Correction: Differential expression of sulfate transporters under selenium supply identifies OsSULTR1;1 as a candidate for nutritional enhancement in super basmati rice - Noreen Aslam; Muhammad Sameeullah; Songul Gurel; Ekrem Gurel (Molecular Biology Reports, 2026)

Differential expression of sulfate transporters under selenium supply identifies OsSULTR1;1 as a candidate for nutritional enhancement in super basmati rice - Noreen Aslam; Muhammad Sameeullah; Songul Gurel; Ekrem Gurel (Molecular Biology Reports, 2026)

Comparative Chloroplast Genomics of Sugar Beet and Wild Relatives: Insights into Photosystem Gene Regulation and Stress Tolerance - Muhammad Sameeullah; Abdullah; Neelam Batool; Ibrar Ahmed; Mehmet Cengiz Baloglu; Noreen Aslam; Mehmet Örgeç; Ekrem Gurel; Mohammad Tahir Waheed; Songul Gurel (Functional & Integrative Genomics, 2026)

Nature-Inspired Nanocomposites for Toxic Heavy Metals Removal: An Overview - Mudassar SanaUllah; Awais Ali Aslam; Abhishek Thakur; Sania Amjad; Shahzaib Ishfaq; Sadaf Ul Hassan; Usman Haidar; Muhammad Shahid Nazir; Mahmood Ahmed; Marek Kowalczuk (Reviews of Environmental Contamination and Toxicology, 2026)

Airborne dust particle-induced lung inflammation in mice alleviated by adipose stem cell-derived conditioned medium - Hazrat Zaman; Madiha Habib; Zobia Safdar; Shafi Zaman; Hafiza Sumbul Yousaf; Muhammad Shahbaz Aslam; Zaigham Abbas (Aerobiologia, 2026)

Genome-wide study uncovering the role of GPAT gene family in watermelon and functional validation of ClGPAT8 against cold stress - Ali Aslam; Xiaomeng Wang; Muhammad Waseem; Muhammad Azam; Ashir Masroor; Qinghua Shi; Sher Muhammad; Aseel Smerat; Muhammad Khuram Razzaq; Ruimin Zhang (Plant Science, 2026)

Streptomyces sp. G21 mitigates postharvest mango anthracnose by tuning ROS and phenylpropanoid metabolism - Yahui Cui; Jinhe Li; Jian Xu; Xiaolei Zhu; Muhammad Muzammal Aslam; Yuanzhi Shao; Rui Li; Wen Li (Food Research International, 2026)

Bacillus subtilis MGRP21 mitigates chromium induced oxidative stress and enhances biomass of Brassica napus L - Shurmeen Qammar; Syeda Sadaf Zehra; Muhammad Naveed Aslam; Anam Moosa; Phyu Shin Thant; Tahir Mahmood; Hongwei Zhao (Physiological and Molecular Plant Pathology, 2026)

Noise ceilings for CO₂–brine interfacial tension machine learning: A physically grounded performance gate from regime-specific ensemble benchmarks - Daniel Tosin Olagunju; Okorie Ekwe Agwu; Muhammad Aslam Md Yusof (International Journal of Greenhouse Gas Control, 2026)

Microplastics in Urban Wastewater: A Vector for Chemical and Biological Pollutants with Emerging Health Risks - Mamoona Sadia; Abid Mahmood; Muhammad Ibrahim; Bilal Aslam (Environmental Research, 2026)

Dopamine Receptor D2 gene Polymorphisms rs2005313, rs4274224, and rs4938019 in Pakistani Patients with Schizophrenia:a Diagnostic Tool for Schizophrenia - Ishrat Yaseen; Saleem Ahmad; Muhammad Ghalib; Muhammad Shahbaz Aslam; Rabbia Tariq; Osheen Sajjad; Faisal Yaseen (Journal of Molecular Neuroscience, 2026)

From lake to plate: microplastic occurrence in freshwater fish and multi-index assessment of human exposure in Kaptai Lake, Bangladesh - Mohammed Manik; Md. Rashedul Haque; Md. Tauhid Hossain; Wahida Ahmed; Md. Rasheduzzaman; Md. Mostafizur Rahman; Muhammad Aslam Ali; Paolo Pastorino (Food Control, 2026)

CRISPR-Cas systems for enhancing chilling tolerance in rice: recent advances and future prospects - Muhammad Sikandar Zaman; Asad Azeem; Ayesha Nouman; Abdullah Khalid; Saira Ghafoor; Muhammad Zia Ul Haq; Muhammad Talha Aslam; Hossam S. El-Beltagi (Biologia Futura, 2026)

Transforming Banana Peel Waste into a Nano Biostimulant: Effects on Maize Seed Germination and Physio-Morphological Traits - Palwasha Sajjad; Umair Riaz; Azer Ahmadov; Tanveer-ul-Haq; Nazar Fareid; Faiza Hassan; Muhammad Adeel; Ayta Umar; Ren Maozhi; Muhammad Usman Aslam; Lamy Hamed (Journal of Plant Growth Regulation, 2026)

Factors influencing circular economy adoption in Pakistan’s construction industry - Rai Waqas Azfar; Mohsin Shah; Mughees Aslam; Muhammad Sohail Anwar Malik; Hamza Alam (Environment, Development and Sustainability, 2026)

Visual analytics of vaccine hesitancy: mapping sentiment and misinformation flows across digital ecosystems - Shahbaz Aslam; Sobia Abid; Arshad Ali; Babar Hussain; Muhammad Zahid Bilal (Next Research, 2026)

Review of risk analysis and management practices for urban water utilities’ sustainability and resilience - Muhammad Fahim Aslam; Farhad Jazaei; Peyman Babakhani; Brian Waldron; Rouzbeh Nazari (Water Resources Management, 2026)
Urban water utilities (UWU) face escalating challenges from rapid urbanization, climate change, aging infrastructure, and institutional fragmentation. This review synthesizes evidence from 62 peer-reviewed studies to critically examine how risk analysis and management are conceptualized and applied in UWU across diverse geographies and economic settings. Through thematic dimensions on geospatial factors, including climate, terrain, population density, Gross Domestic Product (GDP), and water governance structures, along with institutional data, the study employs descriptive patterns, statistical analysis, and cross-regional comparison to explore the distribution and drivers of water risks in UWU. Email correspondence with corresponding authors was conducted to evaluate the implementation status of proposed recommendations and the translation of research findings into practice. The risks are categorized into two types: natural and anthropogenic. The latter includes operational, health and safety, financial, and socio-political risks. The paper evaluates six major risk analysis methodological categories, which vary in terms of data requirements and suitability for different types of risk. These approaches provide valuable interpretations, but many applications represent one issue, often neglecting cascading effects and dynamic interdependencies between risk domains. The review identifies critical research and practice gaps and emphasizes the need for integrated and adaptive risk governance that bridges academic knowledge and utility practice to enhance the resilience of UWU.

Genomic characterization of an isolate of tomato leaf curl New Delhi virus associated with tomato crops - Abdul Majid; Muhammad Taimoor Shakeel; Muhammad Naveed Aslam; Ambreen Maqsood; Muhammad Raheel; Waqas Ashraf; Tahir Farooq; Atta ur Rehman Khan; Mahmoud Ahmed Amer; Mohammed Ali Al-Saleh (European Journal of Plant Pathology, 2026)

Overcoming cellular secretion bottlenecks: advanced secretion engineering and molecular tailoring for next-generation microbial α-amylases with enhanced industrial performance - Saleem Ahmad; Muhammad Nauman Aftab; Muhammad Ghalib; Muhammad Shahbaz Aslam (World Journal of Microbiology and Biotechnology, 2026)

Engineering hybrid hydrogels from sticker–spacer peptide and molybdenum disulfide (MoS2) for advanced antimicrobial therapy - Muhammad Younis; Farhat Rafiq; Shuo Jin; Mussarat Tasleem; Muhammad Saleem; Yongchang Tian; Li Chen; Mohammad Aslam; Dalaver H. Anjum; Jabir Ubaid; Rehan Umer; Xiaofei Chen; et al. (Chemical Engineering Journal, 2026)

Comparative effect assessment of bisphenol analogs by high content analysis in zebrafish (Danio rerio) embryos - Muhammad Arslan Aslam; Riccardo Massei; Stefan Scholz (Aquatic Toxicology, 2026)

Robust fitting of the generalized Pareto distribution for extreme precipitation modeling: a case study in Japan - Muhammad Aslam Mohd Safari; Tosiyuki Nakaegawa; Nurulkamal Masseran (Stochastic Environmental Research and Risk Assessment, 2026)
This study introduces a robust-efficient method for estimating the parameters of the generalized Pareto distribution (GPD), based on the probability integral transform. The probability integral transform estimator (PITE) is designed to enhance robustness in the presence of outliers, a frequent challenge in modeling extreme events. We also study the properties of PITE, including its efficiency and its robustness based on score function and breakdown point, demonstrating its ability to handle extreme data with minimal sensitivity to outliers. In addition, PITE offers computational simplicity, making it accessible for practical applications. Monte Carlo simulations indicate that the PITE family provides a flexible balance between robustness and efficiency: high-efficiency versions perform comparably to traditional estimators for uncontaminated data, while more robust versions often yield smaller deficiencies in simulated scenarios with data contamination. Applied alongside the peaks over threshold approach, PITE effectively models the tail behavior of extreme precipitation events. The method is applied to daily precipitation data from 12 meteorological stations in southern Japan, a region highly susceptible to extreme rainfall due to typhoons and complex climatic factors. Using PITE, GPD parameters are estimated, and return levels for 5-, 10-, 25-, 50-, 100-, and 200-year periods are calculated. The results reveal significant regional variability in extreme precipitation, with stations such as Naze, Miyazaki, and Kumamoto displaying particularly high return levels, indicative of their vulnerability to intense rainfall. The robust application of PITE provides critical insights for flood risk management in southern Japan, particularly in typhoon-prone settings where storm-driven extremes can act as potential outliers, highlighting the importance of localized strategies to mitigate the impact of extreme precipitation events.

Nonstationary generalized extreme value modeling of extreme wind speed events with seasonality and time-varying variability - Jacque Bon-Isaac Aboy; Muhammad Aslam Mohd Safari; Syafrina Abdul Halim (Natural Hazards, 2026)

Application of biogas slurry abate Pb metal uptake and oxidative stress in maize (Zea mays L.) by modulating seedling emergence, antioxidant defense, and root structural–functional traits - Hafeez ur Rehman; Athar Mahmood; Muhammad Shahbaz; Zubair Aslam (BioMetals, 2026)

Pharmacological profiling of medicinal plants: a contemporary overview - Bilal Aslam; Muhammad Rehan Sajid; Asif Hussain; Ifraha Abbas (Natural Product Research, 2026)

The empirical study on the impact of transportation sector, electricity production, and foreign direct investment on carbon emissions in China - Muhammad Umer Aslam; Jiani Wu; Muhammad Kamran Aslam (Environment, Development and Sustainability, 2026)

Hyaluronic acid-functionalized liposomes as a nanoplatform for enhanced pharmacokinetics and therapeutic efficacy in arthritis - Zakir Ali; Muhammad Junaid; Sibgha Batool; Sidra Aslam; Tofeeq ur Rehman; Ali H. Alamri; Adel Al Fatease; Nabil K. Alruwaili; Majed A Alghamdi; Han-Gon Choi; Fakhar ud Din (Journal of Pharmaceutical Investigation, 2026)

Open dumps as a critical source of per- and polyfluoroalkyl substances in agricultural soils of Pakistan: evidence of trifluoroacetic acid dominance - Amina Amanat; Mujtaba Baqar; Maosen Zhao; Faiqa Faryal; Mehmood Aslam; Muhammad Salman Mukhtar; Yiming Yao; Hongwen Sun (Environmental Pollution, 2026)

Petrographic and geomechanical evaluation of nikanai ghar formation (KPK) and kuldana formation (Punjab) rocks: A comparative study for their suitability as building materials in Pakistan - Hassan Ayaz; Jiancong Xu; Sohail Ahmad; Muhammad Usama Aslam (Arabian Journal of Geosciences, 2026)

Sustainable valorization of olive pomace industrial side stream via explainable machine learning guided biochar pyrolysis - Muhammad Ali Haider; Jawad Gul; Muhammad Nouman Aslam Khan; Dagmar Juchelkova (Process Safety and Environmental Protection, 2026)

Mechanistic insights into vanillin's inhibitory effects on Fusarium oxysporum induced postharvest disease - Xinlin Liu; Jiakai He; Yahui Cui; Muhammad Muzammal Aslam; Jian Xu; Rui Li; Wen Li (Postharvest Biology and Technology, 2026)

Projected changes in extreme winds over Japan from a large-ensemble climate experiment - Muhammad Aslam Mohd Safari; Tosiyuki Nakaegawa (Journal of Environmental Management, 2026)

Geochemical dynamics and risk assessment of multi-metal contamination in alluvial soil–rice ecosystems of Pakistan - Waqar Ali; Muhammad Shafeeque; Muhammad Salam; Kang Mao; Muhammad Wajahat Aslam; Hua Zhang; Wei Li (Journal of Environmental Chemical Engineering, 2026)

Probiotic-Derived Bacteriocins for Veterinary Biofilm Control: Mechanisms, Evidence, and One Health Translation - Muhammad Hassan Khalid; Farwa Farooq; Bilal Aslam; Muhammad Saria (Probiotics and Antimicrobial Proteins, 2026)

Plant growth promoting bacteria regulate antioxidant synthesis in wheat under chromium stress leading to stabilization in photosynthetic activity - Modhi O. Alotaibi; Sibgha Noreen; Muhammad Salim Akhter; Tariq Mahmood Khan; Suliman Mohammed Suliman Alghanem; Faizah Amer Altihani; Qafia Naz Aslam; Mohamed Hashem; Omar Mahmoud Al-zoubi (Physiology and Molecular Biology of Plants, 2026)

Artemisia absinthium attenuates hepatic fibrosis in mice by suppressing hepatic stellate cells activation and modulating inflammatory chemokine signaling - Rabbia Manzoor; Iram Gull; Abrar Ahmed; Tuba Ghulam Hussain; Ubaida Hussain; Muhammad Shahbaz Aslam (Cell Biochemistry and Biophysics, 2026)

Retraction notice to ‘Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward’ [Chemosphere 325 (2023) 138367] - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2026)

A comprehensive review on microplastics: Their presence in surface and ground water, environmental distribution, and impact on human and aquatic systems - Khashia Rashid; Shaukat Ali; Asif Hanif Chaudhry; Nosheen Sial; Muhammad Rizwan Akram; Muhammad Aslam (Science of The Total Environment, 2026)

Driving SMEs' international performance: Deciphering the role of strategic orientations and ambidextrous dynamic capabilities in emerging economies - Muhammad Aslam (Next Research, 2026)

Engineering active sites in binary PrCoO3/Mn2V2O7 heterointerface embedded in phosphorus-doped biochar for boosting pH universal water splitting - Sidra Aslam; Muhammad Safdar; Misbah Mirza; Yasir Abbas; Waseem Abbas; Basharat Ali (Fuel, 2026)

Retraction notice to “Comparative study of ZIF-8-materials for removal of hazardous compounds using physio-chemical remediation techniques” [Environ. Res. 220 (2023) 115168] - Bazla Sarwar; Asad Ullah Khan; Muhammad Aslam; Awais Bokhari; Muhammad Mubashir; Asma A. Alothman; Mohamed Ouladsmane; Samar A. Aldossari; Wai Siong Chai; Kuan Shiong Khoo (Environmental Research, 2026)

Optimisation of biomass-derived Propanol–Gasoline blends for sustainable bioenergy utilisation using response surface methodology - Muhammad Arslan Aslam; Ammar Hashmi; Muhammad Ashfaq; Muneeb-ur Rehman; Shah Nawaz Khan; Fakhar-ul Hasnain; Cheol Woo Park (Biomass and Bioenergy, 2026)

Techno-economic analysis and life cycle assessment of integrated carbon capture and methanation using Ni/MgO/Al2O3 dual functional material - Muhammad Saddam Hussain; Yaozu Wang; Bocheng Yu; Yongqing Xu; Haiyang Liu; Muhammad Junaid Aslam; Qinghai Li; Yanguo Zhang; Shaoguang Feng; Xuan Bie; Hui Zhou (Waste Disposal & Sustainable Energy, 2026)

Coated Urea Improves Productivity and Nitrogen Use Efficiency in Wheat - Muhammad Talha Aslam; Imran Khan; Muhammad Umer Chattha; Ghulam Murtaza (Journal of Soil Science and Plant Nutrition, 2026)

Robust fitting of generalized extreme value distribution for extreme wind speeds: a case study using d4PDF data in Japan - Muhammad Aslam Mohd Safari; Tosiyuki Nakaegawa; Nurulkamal Masseran (Environmental and Ecological Statistics, 2026)

Molecular Detection and Phylogenetic Characterization of Avian Infectious Bronchitis Virus (IBV) in Vaccinated Commercial Chicken Flocks Experiencing Outbreaks in Faisalabad, Pakistan - Muhammad Mubeen Ahmad; Muhammad Wasif Gulzar; Muhammad Wasif Azeem; Muhammad Musa Mubashar; Rida Fatima; Muhammad Tayyab Naveed; Muhammad Taha; Sana Riaz; Asad Javed; Mudasser Habib; Rizwan Aslam (Archives of Virology, 2026)

Mechanistic insights into PVC microplastic adsorption on montmorillonite: A first-principles approach toward pollution control - Hafiz Muhammad Umer Aslam; Achintya Bezbaruah; Dmitri Kilin (Environmental Science and Pollution Research, 2026)
Plastic pollution has emerged as a pervasive environmental threat, with polyvinyl chloride (PVC) being a persistent polymer that can degrade into smaller fragments. These particles contaminate aquatic environments, accumulate in biota, and pose serious ecological and health risks. This study used computational methods to investigate the adsorption of vinyl chloride (VC), a PVC oligomer, onto montmorillonite (MMT). Vienna Ab initio Simulation Package was used to perform Density Functional Theory calculations. The interaction between VC and MMT was assessed through binding energy, density of states (DOS), projected DOS, and charge analysis. A negative binding energy (− 0.62 eV) confirmed favorable adsorption. The reduced HOMO–LUMO gap in the VC–MMT hybrid indicated electronic interactions. The orbital-resolved projected density of states (PDOS) showed overlap between the O 2p orbitals of MMT and the H 1 s orbitals of VC. Bader charge analysis revealed negligible charge transfer to the VC molecule upon adsorption, while charge density difference showed localized electron redistribution at the VC–MMT interface. These results indicate a noncovalent interaction without the formation of shared charge density, consistent with polarization-driven physisorption. Molecular dynamics simulations supported these interactions, showing that the VC molecule remained associated with the MMT surface through noncovalent forces. Root mean square deviation (RMSD) confirmed that the VC–MMT structure remained stable throughout the simulation, while the interaction energy exhibited stable fluctuations over time. These findings suggest that MMT holds potential as an effective sink for PVC microplastics through stable, non-covalent surface retention, thereby reducing their dispersion in environmental matrices. Graphical Abstract

A novel solution pollination in orchards - Feiran Wang; Lixing Xie; Yao Zhou; Jiangrui Dai; Likai Feng; Guoli Zhang; Zongcai Zhu; Yancun Zhao; Baolian Tian; Xiuli Shi; Donglan Lv; Muhammad Imran; et al. (Journal of Cleaner Production, 2026)

Arsenic speciation and biogeochemical cycling in Pakistan's alluvial rice ecosystem: Health and trade implications - Waqar Ali; Muhammad Shafeeque; Muhammad Salam; Kang Mao; Muhammad Wajahat Aslam; Sehrish Fatima; Hua Zhang; Wei Li (Environmental Pollution, 2026)

Effectiveness of treatments for propranolol toxicity: a systematic review of current approaches and evidence - Yafei Hu; Khizra Mujahid; Awais Ahsan; Anika Fatima; Inza; Maham Maqsood Ahmed; Maham Anoosh Butt; Sadia Younas; Muhammad Arif Aslam; Hafiz Muhammad Ahmad Javaid (European Journal of Clinical Pharmacology, 2026)

A Novel Homozygous Loss-of-Function Variant in GPR156 Delineates Non-syndromic Hearing Loss - M. Muaaz Aslam; Safdar Abbas; Shoaib Nawaz; Gohar Zaman; Ishtiaq Ahmed; Misbahuddin Rafeeq; Ziaullah M. Sain; Alaa Hamed Habib; Muhammad Umair; Khadim Shah (Biochemical Genetics, 2026)

Evaluation of resistance level of exotic cotton Gossypium hirsutum accession “Mac-07” against cotton leaf curl disease complex - Khalid Pervaiz Akhtar; Sajawal Iqbal; Najeeb Ullah; Muhammad Qasim Aslam; Muhammad Kashif Riaz Khan; Imran Amin (Journal of Plant Pathology, 2026)

Acupuncture as a modulator of microglial polarization and pyroptosis in depression: evidence from a chronic unpredictable mild stress rat model - Xinhong Wu; Zhuoran You; Tiansheng Zhang; Jingyu Zeng; Meng Li; Simin Yan; Jianguo Li; Peng Li; Junliang Shen; Siyu Liu; Muhammad Shahzad Aslam; Jingxuan Li; et al. (Metabolic Brain Disease, 2026)

Tailoring of Cerium Oxide Nanosheets Having Superior Peroxidase Catalytic Activity for Colorimetric Detection of Hydrogen Peroxide - Mohib Ullah; Muhammad Aslam Khan; Sajid Ali; Asfandyar; Zeeshan Tahir; Muhammad Babar Saeed; Vineet Tirth; Ali Algahtani; Ruqia Nazir; Muslim Khan (Journal of Fluorescence, 2026)

Waste-to-resource: Enhanced production of cellulases and lichenase from lignocellulosic biomass via mutated Bacillus subtilis - Junaid Ahmad Raza; Aqsa Aslam; Sibtain Ahmed; Hina Andaleeb; Sheikh Muhammad Yahya Waseem (International Biodeterioration & Biodegradation, 2026)

Integrating nature-inspired optimization techniques and machine learning for accurate CO2/brine interfacial tension estimation: Implications for CO2 sequestration and uncertainty analysis - Joshua Nsiah Turkson; Muhammad Aslam Md Yusof; John Oluwadamilola Olutoki; Bennet Nii Tackie-Otoo; Caspar Daniel Adenutsi; Ingebret Fjelde; Yen Adams Sokama-Neuyam; Victor Darkwah-Owusu (Gas Science and Engineering, 2026)

Dual photo/electrocatalytic CO2 reduction by porphyrin based metal organic framework under visible light and electrochemical bias - Mamuna Aslam; Uzma Saleem; Ibrahim A. Shaaban; Tahani Rahil Aldhafeeri; Ataf Ali Altaf; Muzammil Iqbal; Muhammad Tariq; Mohammed A. Assiri; Shahid Hussain; Hafiz Muhammad Asif (Fuel, 2026)

Development of structurally stable vanadium oxide cathodes featuring tunable ion transport channels via suppressing V O distortion for aqueous zinc ion batteries - Yandong Ma; Qiulin Li; Liang Wang; Weinan Cao; Shu-juan Bao; Muhammad Kashif Aslam; Tong Xue; Maowen Xu (Chemical Engineering Journal, 2026)

Ameliorating effect of veratric acid against mercury-induced neurologic deficit and reproductive toxicity in female rats - Saira Saeed; Qurat-Ul-Ain; Ammara Saleem; Muhammad Imran Khan; Kanwal Akhtar; Aslam Khan; Muhammad Furqan Akhtar; Amir Bouallegue; Mohammed Bourhia; Sultan F. Kadasah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Intravenous thrombolysis as an adjunct to endovascular thrombectomy in acute basilar artery occlusion: a GRADE-assessed systematic review and meta-analysis - Shree Rath; Umama Alam; Aamna Kashif; Muhammad Ansab; Hafiza Tooba Siddiqui; Muhammad Burhan; Zarar Ahmad Khan Afridi; Ahmad Khan; Aiman Gulalay; Bilal Aslam; Raheel Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Extended reduced versus full-dose treatment with factor Xa inhibitors in patients with venous thromboembolism: a GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Umama Alam; Muhammad Abdullah Ali; Muhammad Ansab; Shree Rath; Fazia Khattak; Zaryab Bacha; Hafiza Tooba Siddiqui; Fatima Sajjad; Abdullah Afridi; Zarar Ahmad Khan Afridi; Osama Ahmad; Abdul Moiz; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Anti-arthritic appraisal of Acorus calamus L. extracts in complete Freund’s adjuvant‑induced arthritic Wistar rats via regulating inflammatory cytokines and OPG/RANKL pathway - Muhammad Usman Bari; Asif Hussain; Bilal Aslam; Zia-ud-Din Sindhu; Muhammad Rehan Sajid; Rifat Ullah Khan (Inflammopharmacology, 2026)

Navigating climate policy uncertainty: how innovation and institutional quality drive GHG emissions reduction in G7 countries - Muhammad Asif; Muhammad Azam Zia; Mughair Aslam Bhatti (Clean Technologies and Environmental Policy, 2026)

Investigating the Wound Healing Potential of CuCO3 Nanoparticles in Alloxan-Induced Diabetic Albino Mice: An Experimental and In Silico Approach - Muhammad Saqib Rafiq; Jabbir Ali Khan; Ashfaq Ahmad Shah Bukhari; Samra Shafqat; Ahmad Waheed; Muhammad Yasir Abbas; Muhammad Waseem Aslam; Imran Ibrahim Shaikh; Khalid S. Almaary; Muhammad Saleem Khan (Biological Trace Element Research, 2025)

Lessons from mycorrhizal Synergies: Broad-Leaved trees Boost Chinese fir resilience - Muhammad Ahtesham Aslam; Azra Seerat; Muhammad Younas; Linxin Li; Yachao Li; Pengfei Wu (Rhizosphere, 2025)

First-principles study on structural, elastic, acoustic and optoelectronic properties of hexagonal magnesium oxide (MgO) - Maryam Tariq; Tariq Mahmood; Robina Ashraf; Imran Aslam; Muhammad Rizwan; Arbab Arif; Ch. Omer Javed; Afshan Urooj (Next Research, 2025)

Facile synthesis of novel MgO/NaCl nanosheets for extremely high Ni(II) adsorption from aqueous solutions: Experimental, mathematical, DFT and Box-Behnken design analysis - Khurram Shehzad; Aqdas Shehzad; Mukhtar Ahmad; Hongbo Ou; Suci Meng; Muhammad Aamir Aslam; Umer Farooq; Yan Wang; Min Chen; Yu Gan; Yuanguo Xu (Journal of Environmental Chemical Engineering, 2025)

Phenotypic Plasticity of Safflower Genotypes in Response to Contrasting Climatic Conditions - Obaid Afzal; Mukhtar Ahmed; Sahir Hameed Khattak; Muhammad Aqeel Aslam; Saida Komal; Maryam Murtaza; Farrukh Bashir; Aqeel Ahmad; Aliya Mirbaz; Haroon Ur Rasheed; Ghulam Muhammad Ali; Muhammad Usman; et al. (Plant Molecular Biology Reporter, 2025)

Dynamics of urinary tract infections: a comprehensive study on antimicrobial susceptibility, virulence profiling and molecular epidemiology of uropathogenic Escherichia coli from Pakistan - Zia Ashraf; Muhammad Hidayat Rasool; Bilal Aslam; Hasan Ejaz; Fatima Mujahid; Mohsin Khurshid (Molecular Biology Reports, 2025)

Enhancing Soybean Yields Through Bioinoculants and Topographic Position Site-Specific Management Strategies - Mehtab Muhammad Aslam; Gurbir Singh; Kelly A. Nelson; Gurpreet Kaur (International Journal of Plant Production, 2025)

Mechanistic insight into inflammatory and oxidative stress ameliorating attributes of Atriplex crassifolia 70% ethanol extract against complete Freund’s adjuvant-induced arthritis - Jawaria Khurshid; Anam Iftikhar; Hamza Ahmad Odeibat; Eman Hassan Alshehri; Kiran Aslam; Maria Jaleel; Aymun Jawed; Muhammad Khalid Saeed; Rodney Luwor; Taha Muhammad; Mohammad Saleem; Mohamed Farouk Elsadek (Inflammopharmacology, 2025)

Technological frontiers and optimization in solar power towers: innovations in thermal energy storage, receivers, and heliostat systems - Zeshan Aslam; Syed Ihtsham Ul Haq Gilani; Taib Iskandar Mohamad; Masdi Muhammad; Kehinde Temitope Alao (Clean Technologies and Environmental Policy, 2025)

Green technology, digital transformation, and energy efficiency: driving carbon reduction and waste management innovation in G20 Countries - Muhammad Asif; Muhammad Azam Zia; Muhammad Hashim; Uzair Aslam Bhatti (Clean Technologies and Environmental Policy, 2025)

Prevalence in Relation to Risk Factors of Babesia Bigemina in Bovines of Punjab (Pakistan) - Muhammad Wahab; Mian Abdul Hafeez; Faiza Aslam; Rimsha Farooq; Syeda Anam Sarwar; Waqas Ahmad; Liaqat Ali; Adeel Sattar; Waseem Khan (Acta Parasitologica, 2025)

Faunistics of Syrphid flies (Diptera: Syrphidae) from Chakesar Valley, District Shangla, Pakistan and their biogeographic association - Waqas Ahmad; Jalal Hayat Khan; Qudrat Ullah; Khalid khan; Muhammad Zubair; Sumara Aslam; Muhammad Qasim; Muhammad Ather Rafi (International Journal of Tropical Insect Science, 2025)

Predictive modelling of radon variations in time series using wavelets, multiple linear regression and ARIMA - Nadeem Bashir; Awais Rasheed; Muhammad Osama; Adil Aslam Mir; Muhammad Rafique; Saeed Ur Rahman; Dimitrios Nikolopoulos; Muhammad Abdul Basit; Aftab Alam; Aleem Dad Khan Tareen; Kimberlee Jane Kearfott (Isotopes in Environmental and Health Studies, 2025)

Optimization and comparative modelling of RSM and ANN for the adsorptive removal of Remazol Brilliant Blue R dye using spent coffee ground biochar - Endar Hidayat; Nur Ain Hannani Hamid; Nur Maisarah Mohamad Sarbani; Sadaki Samitsu; Mitsuru Aoyagi; Hiroyuki Harada; Muhammad Aslam Mohd Safari (Chemosphere, 2025)

Contamination and risk assessment of Thallium in the alluvial paddy rice soil system of Pakistan - Waqar Ali; Kang Mao; Muhammad Shafeeque; Muhammad Wajahat Aslam; Hua Zhang; Wei Li (Environmental Research, 2025)

Modelling crop water demand under climate change: the case of Sardinia region - Muhammad Faizan Aslam; Sara Masia; Donatella Spano; Valentina Mereu; Marta Debolini; Richard L. Snyder; Andrea Borgo; Antonio Trabucco (Irrigation Science, 2025)

Efficacy and safety of cyclosporine in colitis: An updated meta-analysis of randomized control trials (1998 to 2024) - Aqsa Mehreen; Faiza Batool; Uzma Azeem Awan; Shaista Aslam; Adnan Haider; Muneeb Ullah; Jin-Wook Yoo; Rida Fatima Saeed; Muhammad Naeem (Inflammopharmacology, 2025)

Multicriteria evaluation of cropland suitability using multisource datasets of satellite remote sensing and ground observation - Danish Raza; Hong Shu; Sahar Mirza; Hasnat Aslam; Aqil Tariq; Rana Waqar Aslam; Hafsa Aeman; Muhsan Ehsan; Maryam Muhammad Ali (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Efficacy and Safety of Mesenchymal Stromal Cells for Steroid-Refractory Acute Graft-versus-Host Disease: An Updated Meta-Analysis of Randomized Controlled Trials - Iftikhar Khan; Umama Rehman; Fatima Aslam; Saad Khan; Umna Bhatti; Hussain Ramzan; Fatima Naveed; Javeria Nawaz; Syeda Malaika Raza; Kiran Inam; Faiza Rajput; Syed Muhammad Seyab; et al. (Stem Cell Reviews and Reports, 2025)

Exogenic Application of Cinnamon Oil and Salicylic Acid Inhibits Alternaria Fruit Rot of Peach by Stimulating Defense-Related Enzymatic Activities - Sadia Hanif; Ambreen Maqsood; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel; Atta ur Rehman; Mohammad Shafiq u Rahman; Shah Saud; Khaled Al-Kahtany; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Bay leaves: the neuroprotective dietary spice via inhibition of amyloid-like aggregation - Nazish Mustafa; Sana Khan; Laila Anwar; Mir Muhammad Uzairullah; Huma Aslam Bhatti; Syed Abid Ali; Ghulam Abbas (Metabolic Brain Disease, 2025)

Predicting ambient PM2.5 levels in the Yangtze River Delta with random forest algorithms: A machine learning approach - Ahmad Hasnain; Muhammad Zaffar Hashmi; Uzair Aslam Bhatti; Basit Nadeem; Geng Wei; Waqas Akram Cheema; Muhammad Asif (Environment, Development and Sustainability, 2025)

Nature-inspired bio-composites for phosphate sequestration and recovery: Green synthesis, mechanistic insights, and multi-stage optimization - Hafiz Muhammad Umer Aslam; Saurabh Singh; Mohiuddin Quadir; Achintya N. Bezbaruah (Science of The Total Environment, 2025)

Enhancing seismic activity classification in augmented soil gas radon time series data through computational intelligence techniques - Nadeem Bashir; Adil Aslam Mir; Muhammad Osama; Saba Maqsood Abbasi; Dimitrios Nikolopoulos; Shahzad Ahmad Qureshi; Muhammad Rafique (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Fertilizing Effects of Ulva intestinalis Derived Bio-Stimulant Enhance Spinacea oleracea L. Production, Nutrient Fluxes and Secondary Metabolism Under NaCl Stress - Sadaf Gul; Hamad Aslam; Muhammad Farrakh Nawaz; Ghulam Yasin; Sana Riaz; Maria Hasnain; Mohamed A. El-Sheikh; Emanuele Radicetti; Zainul Abideen (Journal of Soil Science and Plant Nutrition, 2025)

Managing water deficit in wheat through mulches and irrigation techniques in semi-arid regions - Salman Ahmad; Muhammad Aown Sammar Raza; Muhammad Ali; Rashid Iqbal; Muhammad Usman Aslam; Monika Toleikiene; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Imran Haider; Muhammad Zain; Saltanat Aghayeva; Ozhan Simsek; et al. (Cereal Research Communications, 2025)

Engineered macrophages as versatile platforms for targeted cancer immunotherapy - Khizra Mujahid; Muhammad Arif Aslam; Jutaek Nam; Jeong Uk Choi (Journal of Pharmaceutical Investigation, 2025)

Rhizobacterial diversity exhibiting biotic stress tolerance in association with wheat-cotton crop rotation: Implications for plant–microbe interactions and agroecosystem resilience - Seema Aslam; Muhammad Babar; Ghulam Shabir; Tahir Naqqash; Florian M. W. Grundler (Biologia Futura, 2025)

Synthesis, Spectroscopic, Electronic and Molecular Docking Studies of Pyrazole Based Chalcones as Potential Anticancer Agents - Noreen Aslam; Muhammad Ibrahim; Afifa Yousuf; Muhammad Arif Ali; Jonathan M. White; Ansa Madeeha Zafar; Mussarat Jabeen; Misbahul Ain Khan (Journal of Fluorescence, 2025)

Cumulative effects of ocean currents and land-based pollution on the abundance and composition of coastal zooplankton - Liang-gen Wang; Peng-bing Pei; Muhammad Aslam; Tang-cheng Li; Xiao Ke; Xiu-li Yan; Fei-yan Du; Hong Du (Marine Environmental Research, 2025)

Machine learning assisted predictive urban digital twin for intelligent monitoring of air quality index for smart city environment - Khazina Naveed; Tariq Umer; Aamer Bilal Asghar; Muhammad Aslam; Krzysztof Ejsmont; Ahmed Sayed Mohammed Metwally; Kien Nguyen Thanh (Environmental Modelling & Software, 2025)

Enhancing Salt Tolerance in Tomato Crop Using Microbial Inoculants - Farheen Islam; Afshan Rahman; Hafiza Farhat; Urooj Muhammad Sharif; Nawal Gul; Areeba Aslam (Journal of Crop Health, 2025)

Efficacy of Flumetsulam for Post-Emergence Weed Management in Chickpea (Cicer Arietinum L.) Under the Semi-Arid Region of Pakistan - Muhammad Khuram Razzaq; Ali Aziz; Faisal Hayat; Muhammad Zia Ul Haq; Irfan Rasool; Muhammad Naveed Babur; Ali Aslam; Sher Muhammad; Ammara Tahir; Khalid Hussain (Journal of Crop Health, 2025)

Toxicity of Ethanolic Plant Extracts to Aphis gossypii, Bemisia tabaci, and Frankliniella occidentalis and Selectivity to Coccinella septempunctata and Menochilus sexmaculatus - Moazam Hyder; Faraz Ali; Muhammad Adeel Ghafar; Aslam Bukero; Inzamam ul Haq; Abdul Mubeen Lodhi; Youming Hou (Neotropical Entomology, 2025)

High-performance PVC/polyacrylate-graphene oxide membranes for Pb (II) and Hg (II) ion removal from polluted water: synthesis, characterization, and adsorption studies - Noreen Nasir; Junaid Raza; Abdul Hamid; Naseem Ahmad Khan; Mubushar Majeed; Muhammad Sohail Aslam; Anis Ali Shah; Muhammad Iftikhar; Bilal Arshad; Muhammad Sohail; Muhammad Saeed; Shifa Shaffique; et al. (Environmental Monitoring and Assessment, 2025)

Deciphering the complex roles of leucine-rich repeat receptor kinases (LRR-RKs) in plant signal transduction - Ting Tang; Ferdinand Ndikuryayo; Xue-Yan Gong; Elaheh Amirinezhadfard; Mehtab Muhammad Aslam; Mo-Xian Chen; Wen-Chao Yang (Plant Science, 2025)

Salicylic acid-induced defense responses against a newly identified cotton pathogen, Pantoea vagans - Muneeb Anwer; Muhammad Waqas Azam; Muhammad Taimoor Shakeel; Anam Moosa; Hongwei Zhao; Muhammad Aslam Farooqi; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi; Huda Alghamdi; Ambreen Maqsood; Muhammad Naveed Aslam (Physiological and Molecular Plant Pathology, 2025)

Evaluating the efficacy of nano-cyclosporine A in mice model of ulcerative colitis: a meta-analysis - Aqsa Mehreen; Faiza Batool; Uzma Azeem Awan; Nadia Shabnam; Adnan Haider; Shaista Aslam; Madiha Ghazanfar; Fakhar Ud-Din; Muhammad Irfan Siddique; Muhammad Naeem; Rida Fatima Saeed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Recombinant production and characterization of novel carboxypeptidase from thermophilic archaeon Thermococcus siculi - Saima Iftikhar; Maida Wahid; Muhammad Shahid Nadeem; Farheen Aslam; Khushi Muhammad (Biologia, 2025)

Corrigendum to “Genetic parameters for resistance to field mortality outbreaks and resistance to a pathogenic strain of Vibrio splendidus in Mytilus edulis, Mytilus galloprovincialis and natural hybrid” [Aquaculture, Volume 590] - Munusamy Ajithkumar; Marie Lillehammer; Marie-Agnés Travers; Elise Maurouard; Muhammad Luqman Aslam; Lionel Dégremont (Aquaculture, 2025)

Machine learning approach for photocatalysis: An experimentally validated case study of photocatalytic dye degradation - Hassan Ali; Muhammad Yasir; Hamza Ul Haq; Ali Can Guler; Milan Masar; Muhammad Nouman Aslam Khan; Michal Machovsky; Vladimir Sedlarik; Ivo Kuritka (Journal of Environmental Management, 2025)

Solvothermal synthesis of ruthenium doped MnV2O7@g-C3N4 nanocomposite for oxygen evolution reaction and high-performance asymmetric supercapacitors - Sidra Aslam; Muhammad Safdar; Sadia Akram; Muhammad Awais; Basharat Ali; Yasir Abbas; Waseem Abbas; Misbah Mirza (Journal of Environmental Chemical Engineering, 2025)

Investigation of Photocatalytic and Antibacterial Study of Mo doped ZnCo2O4/rGO Nanohybrid Under Visible Light - Maria Zulfiqar; Gaber A. M. Mersal; Ahmed M. Fallatah; Mohamed M. Ibrahim; Hafiz Muhammad Tahir Farid; Muhammad Aslam; Zeinhom M. El-Bahy (Water, Air, & Soil Pollution, 2025)

Stationary and nonstationary extreme value modeling of maximum temperatures in Peninsular Malaysia using different reanalysis datasets - Hui Qi Chua; Muhammad Aslam Mohd Safari (Theoretical and Applied Climatology, 2025)

Integrated Application of Drought-Tolerant Phosphate Solubilizing Bacteria and Native P Source Improves P Availability with Sustainable Wheat Production - Hafiz Shahid Hussain; Saira Tabbasum; Naima Mahreen; Mahreen Yahya; Khansa Ejaz; Zoya Aslam; Muhammad Imtiaz; Ejaz ul Islam; Zahid Iqbal Sajid; Sumera Yasmin (Journal of Soil Science and Plant Nutrition, 2025)

Effect of Phosphorus Modified Cotton Stick Biochar on Growth, Photosynthesis, Enzymatic Activities and Lead (Pb) Uptake in Tomato Plants Grown in Pb-contaminated Soil - Zaffar Malik; Aleena Shabir; Ahmad Ali; Muhammad Naveed Aslam; Humera Aziz; Syed Farhan Haider Bukhari; Sana Noreen; Usama Ali Tahir; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2025)

Development and Optimization of Stimuli-Responsive Fenugreek/Carrageenan-Co-poly (Methacrylate) Hydrogel Matrices for Controlled Delivery of 5-Fluorouracil - Muhammad Arslan; Muhammad Umer Ashraf; Ayman M. Al-Qaaneh; Aysha Aslam; Asif Mahmood; Hira Ijaz; Rai Muhammad Sarfraz; Mohamed M. Salem; Milad A. Mezher; Mounir M. Bekhit (AAPS PharmSciTech, 2025)

A review on hydrogen production using decorated metal-organic frameworks by electrocatalytic and photocatalytic water splitting - Rana Adeel Mehmood; Awais Ali Aslam; Muhammad Javid Iqbal; Ali Hamza Sajid; Ameer Hamza; Hina Fatima Tahira; Izaz Ul Islam; Erdal Yabalak (Fuel, 2025)

The regulatory role of phytohormones in plant drought tolerance - Zhenqi Liao; Beibei Chen; Hatem Boubakri; Muhammad Farooq; Luis Alejandro Jose Mur; Daisuke Urano; Chee How Teo; Boon Chin Tan; MD Mahadi Hasan; Mehtab Muhammad Aslam; Muhammad Yahya Tahir; Junliang Fan (Planta, 2025)

A multi-dimensional approach to assess crop mapping and farmer strategies in drylands of Bamyan, Afghanistan - Arnaud Caiserman; Sayed Muhammad Baqer Hussaini; Aslam Qadamov; Roy C. Sidle; Aziz Ali Khan (Agricultural Systems, 2025)

Innovative early age mechanical properties of 3D printable mortar enhanced with SBR latex and kaolin - Mazhar Yasin; Zahid Ahmad Siddiqi; Atteq Ur Rehman; Sadaf Noshin; Hafiz Muhammad Shahzad Aslam (European Journal of Environmental and Civil Engineering, 2025)

Impacts of climate change on Pakistan’s weather patterns: a comprehensive study of temperature and precipitation trends - Hafiza Nida; Muhammad Kashif; Azhar Ali Janjua; Muhammad Aslam; Kamil Shahzad Cheema; Sami Ullah (Environmental Monitoring and Assessment, 2025)

Prediction of the salmon lice density on wild sea trout from the mean predicted lice density in the sea: A cross-validation of the data in - Bjarne Gjerde; Muhammad Luqman Aslam (Aquaculture, 2025)

Understanding the Antidepressant Mechanisms of Acupuncture: Targeting Hippocampal Neuroinflammation, Oxidative Stress, Neuroplasticity, and Apoptosis in CUMS Rats - Jianguo Li; Xinhong Wu; Simin Yan; Junliang Shen; Tao Tong; Muhammad Shahzad Aslam; Jingyu Zeng; Yiping Chen; Wenjie Chen; Meng Li; Zhuoran You; Kaiyue Gong; et al. (Molecular Neurobiology, 2025)

Mathematical study of infectious disease of pines caused by bark beetles - Takasar Hussain; Muhammad Ozair; Adnan Aslam; Maham Afaq; Muhammad Tanveer; Muhammad Awais; J. F. Gómez-Aguilar (Modeling Earth Systems and Environment, 2025)

Coral diversity and abundance patterns at the West Coast of Sabah: a case study of Kota Kinabalu coral reefs - Khodzori Fikri Akmal; Nor’ashikin Aslam Zuhairi; Zepri Abdul Muhaimin; Zarinah Waheed; Muhammad Ali Syed Hussein; Gan Sze Hoon; Yee Tong Kiu; Khairul Hisham Hariz; Mazni Muhammad Addin; Siti Nur Hazwani Oslan (Community Ecology, 2025)

Heavy Metal Concentrations in Water, Sediment, and Fish Species in Chashma Barrage, Indus River: A Comprehensive Health Risk Assessment - Khalid Hussain Rind; Sonia Aslam; Nazakat Hussain Memon; Asif Raza; Muhammad Qamar Saeed; Alia Mushtaq; Javed Ahmed Ujan; Syed Fahad Habib; Salim S. Al-Rejaie; Mohamed Mohany (Biological Trace Element Research, 2025)

Eco-friendly herbicide tolerance in maize (Zea mays Linn.) using moringa (Moringa oleifera Lam.) leaf extract - Hameed Ullah Khan; Muhammad Mudasar Aslam; Tahir Iqbal; Amana Khatoon; Muhammad Jamil; Shafiq Ur Rehman; Muhammad Nauman Khan; Majid Iqbal; Alevcan Kaplan; Sarah Abdul Razak; Baber Ali; Muhammad Siddique Afridi; et al. (Acta Physiologiae Plantarum, 2025)

Urea Amidolyase as an Enzyme for Urea Utilisation in Phytoplankton: Functional Display in Chlamydomonas reinhardtii - Honghao Liang; Tangcheng Li; Yuanhao Chen; Jingtian Wang; Muhammad Aslam; Huaizhi Qin; Wenkang Fan; Hong Du; Shuh‐ji Kao; Senjie Lin (Molecular Ecology, 2025)
Urea is an important source of nitrogen for many phytoplankton with the potential to stimulate harmful algal blooms, but the molecular machinery underpinning urea uptake and assimilation by algae is not fully understood. Urease (URE) is commonly regarded as the responsible enzyme, but urea amidolyase (UAL), albeit known to exist, has hardly been studied. Here, the species distribution, expression patterns and functional roles of UAL are examined. We found a widespread occurrence of UAL across six major phytoplankton lineages, along with evidence of a potential URE‐independent evolutionary trajectory and lineage‐specific losses. Quantitative analyses based on marine planktonic metagenomes and metatranscriptomes revealed that UAL is as prevalent as URE, but exhibits higher expression levels in phytoplankton than in bacteria, suggesting that UAL plays a crucial role in nitrogen nutrition in marine phytoplankton. Furthermore, using the CRISPR/Cas9 genome editing method and Chlamydomonas reinhardtii as the algal model, we showed that DUR2 in UAL is essential for urea utilisation, as its knockout completely abolishes the ability of algae to grow under urea as the sole nitrogen source. This study unveils an unappreciated mechanism in algae for utilising urea as a nutrient, underscores the need to consider both URE and UAL enzyme systems to model urea utilisation by algae and provides a crucial gene ( DUR2 ) as a potential genetic marker for detecting the contribution of UAL to urea utilisation in phytoplankton.

Remote sensing-based flash flood mapping and damage assessment in Dera Ismail Khan, Khyber Pakhtunkhwa, Pakistan - Asif Sajjad; Muhammad Ahmad; Rana Waqar Aslam; Mehnaz Bibi; Anwaar Tabassum (Environmental Monitoring and Assessment, 2025)

Production of IgY in egg yolk of Gallus gallus Domesticus by oral vaccination and its characterization with outer membrane of Ornithobacterium rhinotracheale - Muhammad Shahbaz Aslam; Summiya Khalid; Nadia Dar; Zaigham Abbas; Iram Gull; Zoha Khan; Sehreen Ashraf; Zahoor Qadir Samra (Veterinary Immunology and Immunopathology, 2025)

First report of leaf spot of Wodyetia bifurcata caused by Alternaria alternata in Pakistan - Muhammad Abu Bakar; Roshaan Ahmed; Ambreen Maqsood; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel (Physiological and Molecular Plant Pathology, 2025)

Adaptive floristic diversity and ecological responses to environmental gradients in the saline soil ecosystem - Sehrish Sadia; Muhammad Waheed; Fahim Arshad; Abeer Al-Andal; Mubashrah Munir; Asma Jabeen; Samreen Aslam (Journal for Nature Conservation, 2025)

The rise of 4D printing Technology: 2D MXenes for different applications - Iftikhar Hussain; Karanpal Singh; B. Kalidasan; Mubasher Ali; Ke-Juan Meng; Muhammad Kashif Aslam; Sabarison Pandiyarajan; Sajjad Hussain; P. Rosaiah; Saood Ali; Ho-Chiao Chuang; Kaili Zhang (Chemical Engineering Journal, 2025)

Significance of Selenium in Improving the Yield and Quality of Quinoa Under Drought - Muhammad Usman Aslam; Muhammad Aown Sammar Raza; Rashid Iqbal; Salman Ahmad; Imran Haider; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Saltanat Aghayeva; Nazim S. Gruda (Journal of Soil Science and Plant Nutrition, 2025)

Thymol as a Novel Plant-Derived Antibacterial Agent for Suppressing Xanthomonas citri pv. malvacearum in Cotton - Muhammad Naveed Aslam; Huma Khaliq; Hongwei Zhao; Anam Moosa; Ambreen Maqsood; Muhammad Aslam Farooqi; Muhammad Saqib Bilal; Tahir Mahmood; Tariq Mukhtar (Current Microbiology, 2025)

The efficacy of egg albumin nanoparticles adjuvanted Clostridium perfringens type D toxoid vaccine in rabbits - Mehwish Saeed; Saad Zafar; Zarreen Sajjad; Rizwan Aslam; Sultan Ali; Muhammad Shahid Mahmood; Mueed Aayan; Maria Sophy; Saqib Umer; Sajjad Ur Rahman; Muhammad Naveed Anwar (Brazilian Journal of Microbiology, 2025)

Immobilized Chlorella salina for removing nitrogenous and phosphorous compounds from mariculture tail water - Pengbing Pei; Zijie Xie; Muhammad Aslam; Shuangcheng Jiang; Qi Lin; Hongli Cui; Hong Du (Algal Research, 2025)

Growth performance, blood health, and antioxidant status of freshwater carp under brackish water rearing system: Sustainable aquaculture approach in arid and semi-arid conditions - Rabia Tahir; Abdul Ghaffar; Fozia Afzal; Samra; Habiba Jamil; Ume Habiba; Hira Umbreen; Muhammad Sufian; Najat A. Bukhari; Hamid Khan; Husna Aslam; Muhammad Tariq; et al. (Aquaculture, 2025)

Do structural and functional traits modulation determine the ecological fate of castor bean (Ricinus communis L.) under variable pedospheric and atmospheric conditions? - Ummar Iqbal; Muhammad Faisal Gul; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq (South African Journal of Botany, 2025)

Chemically modified filter paper with Jaman fruit extract for visual sensing of milk freshness - Muhammad Naeem Shabbir; Adeel Ahmad; Muhammad Aslam; Ayaz Hassan; Hidayat Ullah; Muhammad Akram; Hafiza Fatima Qayum; Fatima Naeem (Food Chemistry, 2025)

Advances in non-thermal technologies: A revolutionary approach to controlling microbial deterioration, enzymatic activity, and maintaining other quality parameters of fresh stone fruits and their processed products - Kashmala Chaudhary; Samran Khalid; Ammar B. Altemimi; Saqib Abrar; Sadia Ansar; Nabila Aslam; Mudassar Hussain; Rana Muhammad Aadil (Food Chemistry, 2025)

From biochar to battery electrodes: A pathway to green lithium and sodium-ion battery systems - Junaid Aslam; Muhammad Ahsan Waseem; Xiao-Meng Lu; Weiwei Sun; Yong Wang (Chemical Engineering Journal, 2025)

Cooling load reduction strategies for community worship place towards attaining sustainability: a life cycle cost perspective - Fatima Anwar; Muhammad Sohail Anwar Malik; Mughees Aslam; Rai Waqas Azfar Khan (The International Journal of Life Cycle Assessment, 2025)

Evaluation of genetic diversity and population structure of the Chinese chestnut (Castanea mollissima) by using NR-SSR markers - Saman Zulfiqar; Muhammad Mahran Aslam; Allah Ditta; Rashid Iqbal; Abd El-Zaher M. A. Mustafa; Mohamed S. Elshikh; Muhammad Uzair; Saltanat Aghayeva; Muhammad Qasim; Sezai Ercisli; Ozhan Simsek; Tolga Izgu; et al. (Genetic Resources and Crop Evolution, 2025)

Human Plasma-Derived Exosomes: A Promising Carrier System for the Delivery of Hydroxyurea to Combat Breast Cancer - Wajeeha Khalid; Afeefa Aslam; Nadeem Ahmed; Muhammad Sarfraz; Jawad Akbar Khan; Sabeeh Mohsin; Muhammad Shahid Riaz Rajoka; Imran Nazir; Muhammad Imran Amirzada (AAPS PharmSciTech, 2025)

Oral fast dissolving films made with alginate and whey protein for resveratrol delivery - Ziye Xu; Kaiwen Chen; Muhammad Aslam Khan; Li Liang (Journal of Food Engineering, 2025)

Tea polyphenols coating improves physiological properties, microstructure and chemical composition of cuticle to suppress quality deterioration of passion fruit during cold storage - Yu Wang; Wenjun Jia; Xin Wang; Muhammad Muzammal Aslam; Wen Li; Yuanzhi Shao (Food Chemistry, 2025)

Olive oil and castor oil-based self-nanoemulsifying drug delivery system of flurbiprofen can relieve peripheral pain and inflammation through reduction of oxidative stress and inflammatory biomarkers: a comprehensive formulation and pharmacological insights - Mazaghul Basar; Muhammad Imran Khan; Muhammad Furqan Akhtar; Fareeha Anwar; Ammara Saleem; Asadullah Madni; Zulcaif Ahmad; Ali Sharif; Bushra Akhtar; Uzma Shakoor; Aslam Khan (Inflammopharmacology, 2025)

Carvone-loaded chitosan nanoparticles alleviate joint destruction by downregulating the expression of pro, inflammatory cytokines and MMP-13 in adjuvant-induced rat model - Zartashia Kanwal; Bushra Akhtar; Bilal Aslam; Muhammad Imran Arshad (Inflammopharmacology, 2025)

A systematic investigation of multi-attributive border approximation area comparison approach with Gaussian membership function for optimizing water quality - Yasir Yasin; Gulay Demir; Muhammad Riaz; Muhammad Aslam; Dragan Pamucar (Environment, Development and Sustainability, 2024)

Effect of Arsenic Exposure on AS3MT Protein Levels in Serum of Type 2 Diabetic Patients Compared to Non-diabetics - Saima Shokat; Riffat Iqbal; Muhammad Ahmed Ali; Atif Yaqub; Shaista Aslam; Samreen Riaz (Biological Trace Element Research, 2024)

Optimization of cultivation system for Bacillus Siamese strain and its biocontrol effect on postharvest Colletotrichum gloeosporioides - Yuxin Hu; Bo Zhao; Xin Wang; Wenjun jia; Muhammad Muzammal Aslam; Wen Li; Yuanzhi Shao (Postharvest Biology and Technology, 2024)

The CpCOR1 gene enhances cold tolerance and antioxidant activity of papaya fruit in response to postharvest chilling stress - Yuwei Nian; Muhammad Muzammal Aslam; Xin Wang; Hui Gu; Wen Li; Yuanzhi Shao (Postharvest Biology and Technology, 2024)

Overview of industrial food fraud and authentication through chromatography technique and its impact on public health - Nabila Aslam; Rida Fatima; Ammar B. Altemimi; Talha Ahmad; Samran Khalid; Syed Ali Hassan; Rana Muhammad Aadil (Food Chemistry, 2024)

A robust and simple non-enzymatic electrochemical sensor based on carbon dots-metal oxide composite for the detection of metronidazole traces in food products - Hafiza Khadija Aslam; Sehrish Bilal; Sana Mir; Sobia Tabassum; Mazhar Amjad Gilani; Mustansara Yaqub; Muhammad Asim (Food Chemistry, 2024)

Identification of novel antimicrobial compounds in colostrum-associated Lactiplantibacillus plantarum ZFS 1 and 2 by integrating in vitro, machine learning and bioinformatics approaches - Zainab Fiaz; Fatima Noor; Aqsa Ikram; Talha Ali Chohan; Muhammad Zubair Aslam; Najma Arshad (Food Bioscience, 2024)

Modulations in Physiological and Biochemical attributes of Citrus Limon by selenium nanoparticles (SeNPs) under salinity stress - Hummera Nawaz; Khawaja Shafique Ahmad; Iqra Aslam; Athar Mahmood; Ansar Mehmood; Ameer Khan; Muhammad Jamil; Amina Ameer; Muhammad Faraz Khan; Sajjad Hussain (Biocatalysis and Agricultural Biotechnology, 2024)

Molecular genetics, neuroimaging outcomes, and structural analyses of novel and recurrent variants of WDR62 gene in two consanguineous Pakistani families with autosomal recessive primary microcephaly - Komal Aslam; Aysha Saeed; Hafiza Iqra Saeed; Rasheeda Bashir; Hanna Abid; Roeha Akhtar; Nida Habib; Ramisha Khan; Roha Asif; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; et al. (Molecular Biology Reports, 2024)

Investigating the effects of a single ASPM variant (c.8508_8509) on brain architecture among siblings in a consanguineous Pakistani family - Komal Aslam; Aysha Saeed; Iffat Jamil; Hafiza Iqra Saeed; Ramisha Khan; Samina Hassan; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; Rasheeda Bashir; Muhammad Sajid Hussain; Shahid Mahmood Baig; et al. (Molecular Biology Reports, 2024)

Polygonum bistorta Linn. as a green source for synthesis of biocompatible selenium nanoparticles with potent antimicrobial and antioxidant properties - Hafiz Abdul Haseeb; Muhammad Aslam Khan; Hassam Rasheed; Muhammad Usman Zahid; Thu Dung Doan; Muhammad Aamir Ramzan Siddique; Uzair Ahmad; Syed Ali Imran Bokhari (BioMetals, 2024)

In Silico Identification and Characterization of Rare Cold Inducible 2 (RCI2) Gene Family in Cotton - Muhammad Fahad; Leeza Tariq; Muhammad Tanveer Altaf; Muhammad Shahnawaz; Mudassir Aslam; Waqas Liaqat; Inayat Ullah; Izhar Ullah; Heba I. Mohamed; Abdul Basit (Biochemical Genetics, 2024)

Nutritional composition assessment and antimicrobial activity of Catostylus perezi , jellyfish blooms along the coast of Pakistan: an awareness to avoid food neophobia in Pakistan - Muhammad Naveed; Malik Wajid Hussain Chan; Sadar Aslam; Fenghuan Wang; Anas Sajjad; Asad Ullah; Nida Saleem; Muhammad Samee Haider; Victoria Arija (Natural Product Research, 2024)

Recent development towards the novel applications and future prospects for cellulose-metal organic framework hybrid materials: a review - Zeenat Qamar; Awais Ali Aslam; Farheen Fatima; Sadaf Ul Hassan; Muhammad Shahid Nazir; Zulfiqar Ali; Sameer Ahmed Awad; Aqeel Ahmad Khan (Environmental Science and Pollution Research, 2024)

A comprehensive review of remediation strategies for mitigating salt precipitation and enhancing CO2 injectivity during CO2 injection into saline aquifers - Victor Darkwah-Owusu; Muhammad Aslam Md Yusof; Yen A. Sokama-Neuyam; Joshua N. Turkson; Ingebret Fjelde (Science of The Total Environment, 2024)

Reorientation of energy policy and management: Integrated Energy Planning (IEP) framework implementation for Renewable and Thermal Energy Systems (RTES) - Humera Tubussum; Muhammad Aslam; Hezlina Mohd Hashim; Maran Marimuthu; K.H. Mahmoud; Abdullah Saad Alsubaie; Abdul Waheed Bhutto; Aqeel Ahmed Bazmi; Awais Bokhari; Abdul-Sattar Nizami (Process Safety and Environmental Protection, 2024)

Bacillus licheniformis and phytase combination in broiler chicken diets: Effects on growth performance, digestibility coefficients, gut microbiome activities, and bone quality - Jacek Trela; Bartosz Kierończyk; Muhammad Rumman Aslam; Piotr Szymkowiak; Mateusz Rawski; Jerzy Juśkiewicz; Damian Józefiak (Livestock Science, 2024)

Erratum to “Improved project control for sustainable development of construction sector to reduce environment risks” [J. Clean. Product. (2019) 118214] - Summaira Malik; Fareena Fatima; Asma Imran; Lai Fatt Chuah; Jirí Jaromír Klemes; Imran Hameed Khaliq; Saira Asif; Muhammad Aslam; Farrukh Jamil; Abdullah Khan Durrani; Majid Majeed Akbar; Muhammad Shahbaz; et al. (Journal of Cleaner Production, 2024)

Climate change impact on water scarcity in the Hub River Basin, Pakistan - Muhammad Nabeel Aslam; Saqib Ashraf; Sangam Shrestha; Mustajab Ali; Nguyen Cong Hanh (Groundwater for Sustainable Development, 2024)

Exploring fruit ripening methods: Conventional, artificial, and novel approaches for quality and health - Usama Nasir; Amir Ismail; Muhammad Riaz; Kashif Razzaq; Sajid Ali; Ajaz Hussain; Mavra Ameen; Asifa Saif; Farwa Aslam; Carlos Augusto Fernandes de Oliveira (Food Control, 2024)

Leading report regarding the molecular epidemiology of Taenia hydatigena from Pakistan and global overview of the genetic diversity and population structure of the parasite - Naunain Mehmood; Hira Muqaddas; Aqsa Ashraf; Mahnoor Aslam; Maryam Khan; Madiha Fatima; Rahman Qadir; Samir Ibenmoussa; Turki M. Dawoud; Muhammad Irfan Ullah; Furhan Iqbal (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Comprehensive assessment of heavy metal contamination in soil-plant systems and health risks from wastewater-irrigated vegetables - Muhammad Anis Aslam; Muhammad Sohail Abbas; Muhammad Mustaqeem; Maryam Bashir; Adeeba Shabbir; Muhammad Talha Saeed; Rana Muhammad Irfan (Colloids and Surfaces C: Environmental Aspects, 2024)

Conjugated microporous polymers as promising alternatives to traditional electrodes in alkali metal ion batteries - Junaid Aslam; Muhammad Ahsan Waseem; Weiwei Sun; Yong Wang (Chemical Engineering Journal, 2024)

Intraspecific Variation in the Alkaloids of Adalia decempunctata (Coleoptera, Coccinellidae): Sex, Reproduction and Colour Pattern Polymorphism - Muhammad Aslam; Oldřich Nedvěd; John J. Sloggett (Journal of Chemical Ecology, 2024)
In this paper, we examine intraspecific variation in the quantity of alkaloid chemical defence in field collected individuals of the polymorphic ladybird beetle Adalia decempunctata (10-spot ladybird). Like its more widely studied relative Adalia bipunctata (2-spot ladybird), A. decempunctata possesses the alkaloids adaline and adalinine, which are, respectively, the major and minor alkaloids of A. bipunctata . We focused especially on alkaloid concentration in relation to colour pattern morph, sex, and the relationship between female and egg parameters. There was a marked sexual dimorphism in the balance of the two alkaloids, with adaline predominating in females and adalinine predominating in males: in males, on average, over 70% of total alkaloid was adalinine. Females had a lower proportion of adalinine (< 10%) than their eggs (> 15%) and relationships between egg alkaloid and female alkaloid or fecundity were weak or non-existent. Colour pattern morph had a borderline (although not) significant relationship with adaline concentration and total alkaloid concentration, which could be further explored with laboratory reared individuals. The sexual dimorphism in alkaloid content, which seems likely due to differences in synthesis, might be related to their relative costs to the two sexes and might provide insight into the evolution of alkaloid diversity in ladybirds.

Improving salinity tolerance in wheat plants via inoculation with Azospirillum brasilense and Bacillus subtilis for enhanced biomass, growth and physiological process - Nazish Aijaz; Muhammad Saqlain Zaheer; Akhtar Hameed; Hafiz M. Usman Aslam; Muhammad Waqar Alam; Hasan Riaz; Jayanthi Barasarathi; Saltanat Aghayeva; Rani Bibi; Muhammad Waheed Riaz; Hafiz Haider Ali; Salim Manoharadas; et al. (Acta Physiologiae Plantarum, 2024)

Valorization of poultry slaughter wastes via extraction of three structural proteins (gelatin, collagen and keratin): A sustainable approach for circular economy - Muhammad Talha; Muhammad Tanveer; Aqsa Abid; Abid Aslam Maan; Muhammad Kashif Iqbal Khan; Hira Shair; Nimra Tanveer; Almas Mustafa (Trends in Food Science & Technology, 2024)

Surviving the desert's grasp: Decipherment phreatophyte Tamarix aphylla (L.) Karst. Adaptive strategies for arid resilience - Ummar Iqbal; Ali Daad; Ahmad Ali; Muhammad Faisal Gul; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq (Plant Science, 2024)

Prediction of surface urban heat island based on predicted consequences of urban sprawl using deep learning: A way forward for a sustainable environment - Shun Fu; Lufeng Wang; Umer Khalil; Ali Hassan Cheema; Israr Ullah; Bilal Aslam; Aqil Tariq; Muhammad Aslam; Saad S. Alarifi (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Evaluating satellite-based precipitation products for spatiotemporal drought analysis - Hussain Masood Khan; Muhammad Fahim Aslam; Muhammad Waseem; Hafiz Kamran Jalil Abbasi; Ali Iftikhar; Faraz Ul Haq (Journal of Arid Environments, 2024)

Facile synthesis of inherently nitrogen-doped PAN-derived microporous carbons activated with NaNH2 for selective CO2 adsorption and separation - Ghazanfar Nazir; Adeela Rehman; Muhammad Ikram; Muhammad Aslam; Tian C. Zhang; Awais Khalid; Sikandar Aftab; Sajjad Hussain; Hanadi A. Almukhlifi; Amal A. Abdel Hafez; Kwang Heo (Chemical Engineering Journal, 2024)

Revolutionizing soybean genomics: How CRISPR and advanced sequencing are unlocking new potential - Muhammad Khuram Razzaq; Muhammad Naveed Babur; Muhammad Jawad Akbar Awan; Ghulam Raza; Mehwish Mobeen; Ali Aslam; Kadambot H. M. Siddique (Functional & Integrative Genomics, 2024)

Antioxidant dimension and potential as bacterial growth inhibitors in crude extracts of two Artemisia species (Artemisia indica Willd. and Artemisia maritima L.) from Gilgit-Baltistan region, Pakistan - Hassam Rasheed; Adil Hussain; Muhammad Aslam Khan; Mujtaba Hassan; Syed Ali Imran Bokhari (Vegetos, 2024)

Genetic parameters for resistance to field mortality outbreaks and resistance to a pathogenic strain of Vibrio splendidus in Mytilus edulis, Mytilus galloprovincialis and natural hybrid - Munusamy Ajithkumar; Marie Lillehammer; Marie-Agnès Travers; Elise Maurouard; Muhammad Luqman Aslam; Lionel Dégremont (Aquaculture, 2024)

Low mercury risks in paddy soils across the Pakistan - Muhammad Wajahat Aslam; Bo Meng; Waqar Ali; Muhammad Mohsin Abrar; Mahmoud A. Abdelhafiz; Xinbin Feng (Science of The Total Environment, 2024)

Mitigating potential of polystyrene microplastics on bioavailability, uptake, and toxicity of copper in maize (Zea mays L.) - Muhammad Saad Bashir; Umair Saeed; Jawad Aslam Khan; Muhammad Saeed; Ghazala Mustafa; Riffat Naseem Malik (Environmental Pollution, 2024)

Artificial neural network modeling for the prediction, estimation, and treatment of diverse wastewaters: A comprehensive review and future perspective - Muhammad Ibrahim; Adnan Haider; Jun Wei Lim; Bandita Mainali; Muhammad Aslam; Mathava Kumar; Muhammad Kashif Shahid (Chemosphere, 2024)

Cenchrus ciliaris L. ameliorates cigarette-smoke induced acute lung injury by reducing inflammation and oxidative stress - Muhammad Irfan Aslam; Saad Touqeer; QurratUlAin Jamil; Muhammad Irfan Masood; Adeel Sarfraz; Shafaat Yar Khan; Muhammad Saeed Jan; Sulaiman Mohammed Abdullah Alnasser; Ashfaq Ahmad; Fatima Aslam; Shahid Muhammad Iqbal (South African Journal of Botany, 2024)

Aloe vera and tea polyphenols composite coating delays passion fruit senescence by promoting phenolic and flavonoid accumulation - Yu Wang; Muhammad Muzammal Aslam; Xin Wang; Hui Gu; Wenjun jia; Wen Li; Yuanzhi Shao (Food Research International, 2024)

Improving the efficiency of photovoltaic-thermoelectric generator system using novel flying squirrel search optimization algorithm: Hybrid renewable and thermal energy system (RTES) for electricity generation - Muhammad Yaqoob Javed; Aamer Bilal Asghar; Khazina Naveed; Ali Nasir; Basem Alamri; Muhammad Aslam; Essam A. Al-Ammar; Zsolt Conka (Process Safety and Environmental Protection, 2024)

Endophytic Bacillus spp. Mediated Plant Growth Promotion of Tomato Seedlings and Suppression of Meloidogyne incognita and Fusarium oxysporum Disease Complex - Ambreen Maqsood; Muhammad Naveed Aslam; Huma Khaliq; Muhammad Taimoor Shakeel; Haiyan Wu; Shah Fahad (Journal of Plant Growth Regulation, 2024)

Evalution of co-culture system on Debaryomyces hansenii and Bacillus atrophaeus strains and its efficacy on disease control and quality maintenance of postharvest fruit - Zhen Li; Jiayi Li; Muhammad Muzammal Aslam; Shicheng Zou; Rui Li; Wen Li; Yuanzhi Shao (Postharvest Biology and Technology, 2024)

Integrated study of GIS and Remote Sensing to identify potential sites for rainwater harvesting structures - Xingsheng Du; Aqil Tariq; Fakhrul Islam; Samman Aziz; Liaqat Ali Waseem; Muhammad Nasar Ahmad; Muhammad Amin; Naz Ul Amin; Shoaib Ali; Muhammad Aslam; Walid Soufan (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Repurposing of non-steroidal anti-inflammatory drugs for combination therapies to combat multidrug-resistant S. aureus of bovine reproductive tract origin - Painda Bakht; Muhammad Ijaz; Muhammad Zahid Iqbal; Hassaan Bin Aslam; Abdul Rehman (Veterinary Research Communications, 2024)

Recent synthetic approaches towards thienothiophenes: a potential template for biologically active compounds - Ayesha Rafiq; Sana Aslam; Matloob Ahmad; Muhammad Shahid Nazir; Ambar Farooq; Sadia Sultan (Molecular Diversity, 2024)

Plant-Derived Smoke Solution: A Stress Alleviator in Crop - Muhammad Mudasar Aslam; Amana Khatoon; Muhammad Jamil; Shafiq Ur Rehman; Setsuko Komatsu (Journal of Plant Growth Regulation, 2024)

Efficacy of Different Pre and Post Emergence Herbicide Application on Late Sown Maize Crop Under Variable Planting Density - Muhammad Talha Aslam; Rizwan Maqbool; Imran Khan; Muhammad Umer Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Zia Ul Haq; Muhammad Nauman Gulzar; Fatmah M. Alqahtani; Mohamed Hashem; Muhammad Umair Hassan; Sezai Ercisli (International Journal of Plant Production, 2024)

Probabilistic classification of the severity classes of unhealthy air pollution events - Nurulkamal Masseran; Muhammad Aslam Mohd Safari; Razik Ridzuan Mohd Tajuddin (Environmental Monitoring and Assessment, 2024)

Temporal variations of biological nitrogen fixation and diazotrophic communities associated with artificial seaweed farms - Pengbing Pei; Muhammad Aslam; Chunyou Yang; Peilin Ye; Xiao Ke; Zhanhua Liang; Tangcheng Li; Weizhou Chen; Hong Du (Frontiers in Marine Science, 2024)
Diazotrophic communities contribute inorganic nitrogen for the primary productivity of the marine environment by biological nitrogen fixation (BNF). They play a vital role in the biogeochemical cycle of nitrogen in the marine ecological environment. However, there is still an incomplete understanding of BNF and diazotrophs in artificial seaweed farms. Therefore, this study comprehensively investigated the temporal variations of BNF associated with Gracilariopsis lemaneiformis , as well as the diazotrophic communities associated with macroalgae and its surrounding seawater. Our results revealed that a total of 13 strains belonging to Proteobacteria and Bacteroidetes were identified as N 2 -fixing bacteria using azotobacter selective solid medium and nifH gene cloning. Subsequently, BNF and diazotrophic communities were characterized using the acetylene reduction method and high-throughput sequencing of the nifH gene, respectively. The results showed that nitrogenase activity and nifH gene abundance of epiphytic bacteria on G. lemaneiformis varied significantly among four different cultivation periods, i.e., Cultivation Jan. (CJ), Cultivation Feb. (CF), Cultivation Mar. (CM), Cultivation Apr. (CA). Among them, the nitrogenase activity and nifH gene abundance of epiphytic bacteria on G. lemaneiformis in CM were significantly higher than those in CJ, CF, and CA, indicating that the BNF of eiphytic bacteria on G. lemaneiformis was markedly enhanced. Combined with the data on environmental factors, it was found that the low concentration of nitrogen and phosphorus in CM might considerably boost the BNF of epiphytic bacteria in G. lemaneiformis . The sequencing results of the nifH gene showed that the α-diversity of diazotrophic communities associated with G. lemaneiformis and seawater in CM was higher than that in other cultivation periods. In addition, the diazotrophic communities on G. lemaneiformis were significantly different in CJ, CF, CM, and CA, and they were significantly diverse from diazotrophic communities in seawater. LEfSe analysis indicated that Rhodobacterales, Hyphomonadaceae, Robiginitomaculum , and Robiginitomaculum antarcticum within α-proteobacteria played a remarkable role in BNF in response to nitrogen nutrient deficiency. Taken together, these results provide a unique insight into the interaction between macroalgae and its epiphytic bacteria and lay a foundation for further research on the mechanism of action of nitrogen-cycling microorganisms associated with macroalgae.

Cryptic footprint of thallium in soil-plant systems; A review - Noman Shakoor; Samama Tariq; Muhammad Adeel; Imran Azeem; Muhammad Nadeem; Muhammad Zain; Yuanbo Li; Wang Quanlong; Rabia Aslam; Yukui Rui (Chemosphere, 2024)

Monitoring landuse change in Uchhali and Khabeki wetland lakes, Pakistan using remote sensing data - Rana Waqar Aslam; Hong Shu; Aqil Tariq; Iram Naz; Muhammad Nasar Ahmad; Abdul Quddoos; Kanwal Javid; Farhan Mustafa; Hafsa Aeman (Gondwana Research, 2024)

Predicting ambient PM2.5 concentrations via time series models in Anhui Province, China - Ahmad Hasnain; Muhammad Zaffar Hashmi; Sohaib Khan; Uzair Aslam Bhatti; Xiangqiang Min; Yin Yue; Yufeng He; Geng Wei (Environmental Monitoring and Assessment, 2024)

Assessment of heavy metals level in chicken with indeterminate analysis in localities of Lahore, Pakistan - Naveed Ahmad; Usama Afzal; Ramna Zafar; Muhammad Arslan; Saira Riaz; Shahzad Naseem; Muhammad Naeem; Adeena Fatima; Mubashar Ali; Muhammad Aslam (Environmental Monitoring and Assessment, 2024)

Development of a robust method for Cd(II) ions analysis using CeO2- and CeO2-Cu-BTC-based electrochemical sensors - Sabah Haider; Maria Zaib; Umar Farooq; Muhammad Salman; Rabia Akram Bajwa; Shabnam Shahida; Muhammad Aslam (Environmental Monitoring and Assessment, 2024)

An appealing review of industrial and nutraceutical applications of pistachio waste - Syed Ali Hassan; Mueen Abbas; Sania Zia; Abid Aslam Maan; Muhammad Kashif Iqbal Khan; Abdo Hassoun; Aamir Shehzad; Richard Gattin; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2024)

Evaluation of soil texture classification from orthodox interpolation and machine learning techniques - Lei Feng; Umer Khalil; Bilal Aslam; Bushra Ghaffar; Aqil Tariq; Ahsan Jamil; Muhammad Farhan; Muhammad Aslam; Walid Soufan (Environmental Research, 2024)

Expression of BSN314 lysozyme genes in Escherichia coli BL21: a study to demonstrate microbicidal and disintegarting potential of the cloned lysozyme - Muhammad Naveed; Sai Wen; Malik Wajid Hussain Chan; Fenghuan Wang; Sadar Aslam; Xian Yin; Baocai Xu; Asad Ullah (Brazilian Journal of Microbiology, 2024)

Optimizing electroactive membrane performance for microalgae harvesting: A response surface methodology study of membrane formulation and operating parameters for electro filtration - Azeem Mushtaq; Hoon Cho; Asma Batool; Muhammad Tahir Fazal; Muhammad Aslam; Muhammad Saif UR. Rehman; Jason Chun-Ho Lam; Jong-In Han (Chemosphere, 2024)

First insights into per-and polyfluoroalkyl substance contamination in edible fish species of the Indus water system of Pakistan - Rahat Riaz; Muhammad Yasir Abdur Rehman; Muhammad Junaid; Taimoor Iqbal; Jawad Aslam Khan; Yanran Dong; Linxia Yue; Yupeng Chen; Nan Xu; Riffat Naseem Malik (Chemosphere, 2024)

Effects of selenium on biogeochemical cycles of cadmium in rice from flooded paddy soil systems in the alluvial Indus Valley of Pakistan - Waqar Ali; Kang Mao; Muhammad Shafeeque; Muhammad Wajahat Aslam; Wei Li (Science of The Total Environment, 2024)

Marshall-Olkin length biased exponential distribution for wind speed analysis alternative to Weibull distribution - Muhammad Ahsan ul Haq; Sharqa Hashmi; Muhammad Aslam (Modeling Earth Systems and Environment, 2024)

Development and Characterization of Glimepiride-Loaded Polymeric Nanoparticles: Formulation Design and Evaluation - Zaiba Irfan; Muhammad Imran Khan; Muhammad Farhan Sohail; Muhammad Furqan Akhtar; Muhammad Naeem Qaisar; Muhammad Kashif Javed; Fareeha Anwar; Badarqa-tul-Ayesha; Majid Anwar; Aslam Khan; Faizan Akram (Journal of Pharmaceutical Innovation, 2024)

Intraspecific and interspecific comparison of toxicity of ladybirds (Coleoptera: Coccinellidae) with contrasting colouration - Muhammad Aslam; Oldřich Nedvěd (Zoology, 2024)

Microbial activity, community composition and degraders in the glyphosate-spiked soil are driven by glycine formation - Sohaib Aslam; Muhammad Arslan; Karolina M. Nowak (Science of The Total Environment, 2024)

Nanoscale enhancements in perovskite-based photovoltaics - Sikandar Aftab; Xin Li; Sajjad Hussain; Muhammad Aslam; Altaf Hussain Rajpar; Abdullah G. Al-Sehemi (Chemical Engineering Journal, 2024)

Detection of high-risk human papillomavirus infected cervical biopsies samples by immunohistochemical expression of the p16 tumor marker - Muhammad Shafique; Iqra Shoaib; Bilal Aslam; Rabia Khalid; Imrana Tanvir; Muhammad Hidayat Rasool; Tawaf Ali Shah; Khalid S. Almaary; Mohammed Bourhia; Muhammad Usman Qamar (Archives of Microbiology, 2024)

Does the impact of financial development reinforce sustainability ecological footprint? Fresh evidence from middle and high-income economies - Bilal Aslam; Guitao Zhang; Muhammad Asif Amjad; Shujun Guo; Maowang Ji (Journal of Cleaner Production, 2023)

Unraveling the defensive strategies of camel thorn Alhagi maurorum medik. For thriving in arid and semi-arid environments - Ummar Iqbal; Ahmad Ali; Ali Daad; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq; Muhammad Faisal Gul (Journal of Arid Environments, 2023)

pH-driven preparation of caseinate-chitosan complex coacervation for co-encapsulation of hydrophobic curcumin and hydrophilic l-ascorbate: Stability and in vitro release properties - Xin Yin; Muhammad Aslam Khan; Paul Van der Meeren; Shuai Feng; Yongchao Wang; Li Liang (Food Bioscience, 2023)

Rainwater harvesting for agriculture development using multi-influence factor and fuzzy overlay techniques - Xiangtian Zheng; Abid Sarwar; Fakhrul Islam; Abdul Majid; Aqil Tariq; Muhammad Ali; Shazia Gulzar; Muhammad Ismail Khan; Muhammad Akmal Sardar Ali; Muhammad Israr; Ahsan Jamil; Muhammad Aslam; et al. (Environmental Research, 2023)

Water Waste Monitoring Using Neutrosophic Multivariate T2 Control Chart - Muhammad Kashif; Abdullah M. Almarashi; Muhammad Aslam; Muhammad Imran Khan (Water, Air, & Soil Pollution, 2023)

Developing Micropropagation Protocols of Date Palm (Phoenix dactylifera L.) cv. Barhi Using Shoot Tip Explants - Najamuddin Solangi; Adel Ahmed Abul-Soad; Mushtaque Ahmed Jatoi; Ghulam Sarwar Markhand; Muhammad Aslam Solangi; Abdul Aziz Mirani (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Curative potential of Populus ciliata Wall ex. Royle extract against adjuvant-induced arthritis and peripheral neuropathy in Wistar rats - Amna Tahir; Muhammad Furqan Akhtar; Ammara Saleem; Muhammad Naveed; Basiru Olaitan Ajiboye; Fareeha Anwar; Aslam Khan (Inflammopharmacology, 2023)

Heavy metals contamination in vegetables irrigated with wastewater: a case study of underdeveloping regions of Pakistan - Ana Aslam; Asifa Naz; Syed Shahid Hussain Shah; Farah Rasheed; Raheela Naz; Amina Kalsom; Nisa Mukhtar; Abid Niaz; Muhammad Aftab; Irfan Rasheed; Muhammad Arfan Ul Haq; Muhammad Arif; et al. (Environmental Geochemistry and Health, 2023)

Effect of Dietary Supplementation of Zinc Nanoparticles Prepared by Different Green Methods on Egg Production, Egg Quality, Bone Mineralization, and Antioxidant Capacity in Caged Layers - Safdar Hassan; Muhammad Sharif; Muhammad Aslam Mirza; Muhammad Saif ur Rehman (Biological Trace Element Research, 2023)

Characterization for optimizing the integrated management of solid waste for energy recovery and circular economy - Fariha Jabeen; Muhammad Adrees; Muhammad Ibrahim; Muhammad Waqas; Abid Mahmood; Uzma Noreen; Afifa Aslam (Environmental Science and Pollution Research, 2023)

The nutraceutical properties and health benefits of pseudocereals: a comprehensive treatise - Muhammad Shahbaz; Nighat Raza; Mahad Islam; Muhammad Imran; Ishtiaque Ahmad; Arun Meyyazhagan; Karthika Pushparaj; Balamuralikrishnan Balasubramanian; Sungkwon Park; Kannan R. R. Rengasamy; Tanweer Aslam Gondal; Ahmed El-Ghorab; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Formation and characterization of hollow particles with zein-WPI hybrid shell for curcumin encapsulation - Qianqian Shen; Kaiwen Chen; Muhammad Aslam Khan; Li Liang (Food Hydrocolloids, 2023)

Bionanocomposite scaffolds based on MnS-nanorods loaded acacia-Senegal-gum hydrogels: Fabrication, characterization and biological evaluation - Hidayat Ullah; Junaid Ihsan; Rasha M.K. Mohamed; Muhammad Aslam Khan; Marvi Ghani; Naseem Rauf; Shafqat Ullah; Asif Javed; Muhammad Farooq (Bioactive Carbohydrates and Dietary Fibre, 2023)

Survival tactics of an endangered species Withania coagulans (Stocks) Dunal to arid environments - Ummar Iqbal; Fahad Ur Rehman; Muhammad Usama Aslam; Muhammad Faisal Gul; Umar Farooq; Amina Ameer; Naila Asghar; Ansar Mehmood; Khawaja Shafique Ahmad (Environmental Monitoring and Assessment, 2023)

First report of Geotrichum candidum causing rose blight disease in Pakistan - Muhammad Talha Ikram; Muhammad Naveed Aslam; Anam Moosa; Faisal Zulfiqar; Muhammad Taimoor Shakeel; Roshaan Ahmed; Muneeb Anwer; Atta ur Rehman Khan (Journal of Plant Pathology, 2023)

Utilization of cereal-based husks to achieve sustainable development goals: Treatment of wastewater, biofuels, and biodegradable packaging - Syed Ali Hassan; Mueen Abbas; Waqar Mujahid; Waqar Ahmed; Saeed Ahmad; Abid Aslam Maan; Aamir Shehzad; Zuhaib F. Bhat; Rana Muhammad Aadil (Trends in Food Science & Technology, 2023)

Unraveling the effects of zinc sulfate nanoparticles and potassium fertilizers on quality of maize and associated health risks in Cd contaminated soils under different moisture regimes - Muhammad Umair; Sehrish Huma Zafar; Mumtaz Cheema; Rashid Minhas; Abdul Manan Saeed; Muhammad Saqib; Muhammad Aslam (Science of The Total Environment, 2023)

Cellulose-based adsorbent materials for water remediation: Harnessing their potential in heavy metals and dyes removal - Awais Ali Aslam; Sadaf Ul Hassan; Muhammad Haris Saeed; Osama Kokab; Zulfiqar Ali; Muhammad Shahid Nazir; Waleed Siddiqi; Aamir Ali Aslam (Journal of Cleaner Production, 2023)

Recent advances in biological hydrogen production from algal biomass: A comprehensive review - Ayesha Aslam; Ali Bahadar; Rabia Liaquat; Muhammad Muddasar (Fuel, 2023)

Effects of citrus pomace on mechanical, sensory, phenolic, antioxidant, and gastrointestinal index properties of corn extrudates - Muhammad Asif; Muhammad Kashif Iqbal Khan; Muhammad Issa Khan; Abid Aslam Maan; Harrison Helmick; Jozef L. Kokini (Food Bioscience, 2023)

Evaluation of possible attenuative role of chrysoeriol against polyethylene microplastics instigated testicular damage: A biochemical, spermatogenic and histological study - Muhammad Umar Ijaz; Faria Saher; Nemra Aslam; Ali Hamza; Haseeb Anwar; Saad Alkahtani; Hammad Ahmad Khan; Mian Nadeem Riaz (Food and Chemical Toxicology, 2023)

Scavenging rate of palatable and toxic arthropod carrions during day and night - Muhammad Aslam; Oldřich Nedvěd (Biologia, 2023)

Translating environmental corporate social responsibility into environmental performance and competitive advantage: a moderated mediation model - Ahmad Qammar; Rabiya Sagheer; Muhammad Shakeel Aslam (Environmental Science and Pollution Research, 2023)

Coating of DNA and DNA complexes on zein particles for the encapsulation and protection of kaempferol and α-tocopherol - Chuye Ji; Muhammad Aslam Khan; Kaiwen Chen; Li Liang (Journal of Food Engineering, 2023)

Polyoxyethylene Lauryl Ether (Brij-35) and Poloxamer 407–Based Non-ionic Surfactant Vesicles for Dissolution Enhancement of Tacrolimus - Razia Hanif; Muhammad Imran Khan; Asadullah Madni; Muhammad Furqan Akhtar; Muhammad Farhan Sohail; Ammara Saleem; Mubashar Rehman; Sufyan Junaid Usmani; Aslam Khan; Athar Masood (Journal of Pharmaceutical Innovation, 2023)

Transforming Lignin Biomass to Value: Interplay Between Ligninolytic Enzymes and Lignocellulose Depolymerization - Namra Ahmad; Shakira Aslam; Nazim Hussain; Muhammad Bilal; Hafiz M. N. Iqbal (BioEnergy Research, 2023)
Lignin is the main constituent of lignocellulosic biomasses, which have a significant untapped ability to replace ecologically unfavorable and non-renewable fossil fuels. The lignin is broken down by ligninolytic bacteria, which also use a peripheral pathway to transform heterogeneous lignin derivatives into central intermediates like protocatechuate or catechol. By undergoing ring cleavage through the -ketoadipate pathway, these intermediates become metabolites by producing acetyl-CoA for internal product biosynthesis, including the creation of triacylglycerols and polyhydroxyalkanoates. Expanding our understanding of ligninolytic microbial communities, strains, and enzymes through bioprospecting can help us better understand the metabolism of aromatics. The most viable idea for sustainable development is the valorization of lignin into biopolymers as well as other high-value goods. This process is now being used to generate a variety of biopolymers, including polyesters, epoxies, phenol resins, poly (lactic acids), poly hydroxyl alkanoates, and polyurethanes. Furthermore, lignin recalcitrance remained a possible barrier to efficient lignin valorization, prompting several efforts to design high-efficiency bioprocesses to produce specific polymer types as well as other important bioproducts. Graphical Abstract

Investigation of the incidence of heavy metals contamination in commonly used fertilizers applied to vegetables, fish ponds, and human health risk assessments - Samiyah Tasleem; Samrah Masud; Syed Sikandar Habib; Saira Naz; Francesco Fazio; Muhammad Aslam; Mujeeb Ullah; Sobia Attaullah (Environmental Science and Pollution Research, 2023)

An insight into the hepatoprotective role of Velpatasvir and Sofosbuvir per se and in combination against carbon tetrachloride-induced hepatic fibrosis in rats - Sadaf Yasmeen; Aslam Khan; Fareeha Anwar; Muhammad Furqan Akhtar; Sidra Yasmeen; Shafeeq Ali Shah (Environmental Science and Pollution Research, 2023)

Sn-doped nanoconfinements of SBA-15 for oxidative desulfurization: Kinetics and thermodynamics - Mateen Ahmad; Sobia Aslam; Fazle Subhan; Liu Zhen; Zifeng Yan; Muhammad Yaseen; Muhammad Ikram; Afaq Nazir (Fuel, 2023)

Microwaves as sustainable approach for artificial ripening of date fruit cv. Khupra to reduce fruit waste - Tayyaba Alvi; Muhammad Kashif Iqbal Khan; Abid Aslam Maan; Muhammad Shahid; Shyam Sablani (Food Bioscience, 2023)

Anti-arthritic effects of geranium essential oil loaded chitosan nanoparticles in Freund’s complete adjuvant induced arthritic rats through down-regulation of inflammatory cytokines - Rana Dawood Naseer; Faqir Muhammad; Bilal Aslam; Muhammad Naeem Faisal (Inflammopharmacology, 2023)

Assessment of heavy metals and associated oxidative stress in occupationally exposed workers from Bannu and Karak Districts in Pakistan - Kaleem Khan; Muhammad Tariq Rafiq; Aziz-Ur-Rahim Bacha; Iqra Nabi; Muhammad Irshad; Faridullah Faridullah; Muhammad Younas; Muhammad Daud Khan; Rukhsanda Aziz; Muhammad Amin; Awais Arifeen; Sohaib Aslam; et al. (Environmental Geochemistry and Health, 2023)

Sustainable utilization of apple pomace and its emerging potential for development of functional foods - Muhammad Asif; Tahreem Javaid; Zafar Ullah Razzaq; Muhmmad Kashif Iqbal Khan; Abid Aslam Maan; Saria Yousaf; Ayesha Usman; Sidra Shahid (Environmental Science and Pollution Research, 2023)

Assessment of lead, cadmium, and mercury levels in the breast milk in Pakistani women - Naveed Ahmad; Abbas Muhammad; Ramna Zafar; Usama Afzal; Muhammad Aslam (Environmental Science and Pollution Research, 2023)

The potential of functionalized graphene-based composites for removing heavy metals and organic pollutants - Muhammad Saqlain Iqbal; Awais Ali Aslam; Ramsha Iftikhar; Muhammad Junaid; Syed Muhammad Imran; Muhammad Shahid Nazir; Zulfiqar Ali; Muhammad Zafar; Ayesha Kanwal; Norinsan Kamil Othman; Ujjwal Pal; Ai Ling Pang; et al. (Journal of Water Process Engineering, 2023)

Sublethal effects of spinetoram and emamectin benzoate on key demographic parameters of fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) under laboratory conditions - Arzlan Abbas; Chen Ri Zhao; Muhammad Arshad; Xiao Han; Ayesha Iftikhar; Faisal Hafeez; Asad Aslam; Farman Ullah (Environmental Science and Pollution Research, 2023)

RETRACTED: Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2023)

A graft that crafts nontransgenic and genome-edited plants - Muhammad Jawad Akbar Awan; Muhammad Qasim Aslam; Rubab Zahra Naqvi; Imran Amin; Shahid Mansoor (Trends in Plant Science, 2023)

Pterostilbene reduces the progression of atopic dermatitis via modulating inflammatory and oxidative stress biomarkers in mice - Yasmin Bangash; Ammara Saleem; Muhammad Furqan Akhtar; Fareeha Anwar; Bushra Akhtar; Ali Sharif; Muhammad Imran Khan; Aslam Khan (Inflammopharmacology, 2023)

First record of Fusarium solani causing post-harvest Fusarium rot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Faisal Zulfiqar; Muhammad Naveed Aslam (Journal of Plant Pathology, 2023)

First report of leaf spot of Aloe vera caused by Curvularia spicifera in Pakistan - Roshaan Ahmed; Muhammad Naveed Aslam; Anam Moosa; Muhammad Taimoor Shakeel; Ambreen Maqsood (Journal of Plant Pathology, 2023)

Municipal solid waste treatment for bioenergy and resource production: Potential technologies, techno-economic-environmental aspects and implications of membrane-based recovery - Naila Amin; Muhammad Aslam; Zakir khan; Muhammad Yasin; Shakhawat Hossain; Muhammad Kashif Shahid; Abrar Inayat; Ahmed Samir; Rizwan Ahmad; Mohammad N. Murshed; Muhammad Shahzad Khurram; Mohamed E. El Sayed; et al. (Chemosphere, 2023)

Macroalgal biochar synthesis and its implication on membrane fouling mitigation in fluidized bed membrane bioreactor for wastewater treatment - Muhammad Maaz; Muhammad Aslam; Muhammad Yasin; Asim Laeeq Khan; Azeem Mushtaq; Tahir Fazal; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Jeonghwan Kim (Chemosphere, 2023)

Phytotoxic responses of wheat to an imidazolium based ionic liquid in absence and presence of biochar - Taza Gul; Muhammad Mudasar Aslam; Amir Sada Khan; Tahir Iqbal; Faizan Ullah; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Muhammad Saeed Akhtar (Chemosphere, 2023)

A review on covalent organic frameworks as adsorbents for organic pollutants - Awais Ali Aslam; Adnan Irshad; Muhammad Shahid Nazir; Muhammad Atif (Journal of Cleaner Production, 2023)

On ranking climate factors affecting the living organisms based on paired comparison model, a Bayesian approach - Khalil Ullah; Muhammad Aslam; Nasir Abbas; Syed Irfan Shah (Climate Dynamics, 2023)

Effect of exogenous taurine on pea (Pisum sativum L.) plants under salinity and iron deficiency stress - Muhammad Arslan Ashraf; Rizwan Rasheed; Muhammad Rizwan; Iqbal Hussain; Ramish Aslam; Freeha Fatima Qureshi; Barira Shoukat Hafiza; Rohina Bashir; Shafaqat Ali (Environmental Research, 2023)

DOM influences Hg methylation in paddy soils across a Hg contamination gradient - Mahmoud A. Abdelhafiz; Jiang Liu; Tao Jiang; Qiang Pu; Muhammad Wajahat Aslam; Kun Zhang; Bo Meng; Xinbin Feng (Environmental Pollution, 2023)

Functional characterization of transcriptional activator gene SIARRI in tomato reveals its role in fruit growth and ripening - Muhammad Fahad; Muhammad Tanveer Altaf; Amna Jamil; Abdul Basit; Muhammad Mudassir Aslam; Waqas Liaqat; Muhammad Nadeem Shah; Izhar Ullah; Heba I. Mohamed (Transgenic Research, 2023)

Fabrication of whey-protein-stabilized G/O/W emulsion for the encapsulation and retention of -ascorbic acid and α-tocopherol - Muhammad Aslam Khan; Huayan Bao; Hao Cheng; Shuai Feng; Yanmei Wang; Li Liang (Journal of Food Engineering, 2023)

Thermal degradation characteristics, kinetic and thermodynamic analyses of date palm surface fibers at different heating rates - Abrar Inayat; Farrukh Jamil; Shams Forruque Ahmed; Muhammad Ayoub; Peer Mohamed Abdul; Muhammad Aslam; M. Mofijur; Zakir Khan; Ahmad Mustafa (Fuel, 2023)

RETRACTED: Comparative study of ZIF-8-materials for removal of hazardous compounds using physio-chemical remediation techniques - Bazla Sarwar; Asad Ullah Khan; Muhammad Aslam; Awais Bokhari; Muhammad Mubashir; Asma A. Alothman; Mohamed Ouladsmane; Samar A. Aldossari; Wai Siong Chai; Kuan Shiong Khoo (Environmental Research, 2023)

Bombax ceiba flower extract mediated synthesis of Se nanoparticles for antibacterial activity and urea detection - Muhammad Safdar; Sidra Aslam; Misbah Akram; Adnan Khaliq; Samreen Ahsan; Atif Liaqat; Misbah Mirza; Muhammad Waqas; Waseem Akhtar Qureshi (World Journal of Microbiology and Biotechnology, 2023)

Assessing the ambient air quality patterns associated to the COVID-19 outbreak in the Yangtze River Delta: A random forest approach - Ahmad Hasnain; Yehua Sheng; Muhammad Zaffar Hashmi; Uzair Aslam Bhatti; Zulkifl Ahmed; Yong Zha (Chemosphere, 2023)

Task-specific polymeric membranes to achieve high gas-liquid mass transfer - Muhammad Tayyab Khalid; Tanzila Anjum; Asim Laeeq Khan; Fahad Rehman; Muhammad Aslam; Mazhar Amjad Gilani; Faheem Hassan Akhtar; Mungyu Lee; In Seop Chang; Muhammad Yasin (Chemosphere, 2023)

Deep reinforcement learning-based long-range autonomous valet parking for smart cities - Muhammad Khalid; Liang Wang; Kezhi Wang; Nauman Aslam; Cunhua Pan; Yue Cao (Sustainable Cities and Society, 2023)

Prediction and interpretation of antibiotic-resistance genes occurrence at recreational beaches using machine learning models - Sara Iftikhar; Asad Mustafa Karim; Aoun Murtaza Karim; Mujahid Aizaz Karim; Muhammad Aslam; Fazila Rubab; Sumera Kausar Malik; Jeong Eun Kwon; Imran Hussain; Esam I. Azhar; Se Chan Kang; Muhammad Yasir (Journal of Environmental Management, 2023)

A review of potential antibacterial activities of nisin against Listeria monocytogenes: the combined use of nisin shows more advantages than single use - Mengjie Wu; Yue Ma; Xin Dou; Muhammad Zohaib Aslam; Yangtai Liu; Xuejuan Xia; Shuo Yang; Xiang Wang; Xiaojie Qin; Takashi Hirata; Qingli Dong; Zhuosi Li (Food Research International, 2023)

Production performance, protein digestibility, gut health and economic efficiency in sexed broilers with super dozing of lysine - Najam us Sahar; Muhammad Shoaib; Muhammad Aslam Mirza; Shaukat Ali Bhatti; Shahzad Ashraf; Noreen Aslam; Alishbah Roobi; Muhammad Arslan Asif (Tropical Animal Health and Production, 2023)

Effects of age, body weight, semen collection frequency and holding duration on semen traits of broiler breeder reared under different housing systems - Muhammad Shabir Shaheen; Sadaf Aslam; Shahid Mehmood; Muhammad Tariq; Yassar Abbas; Hassan Ashfaq; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Prospects of antimicrobial peptides as an alternative to chemical preservatives for food safety - Iqra Kamal; Usman Ali Ashfaq; Sumreen Hayat; Bilal Aslam; Muhammad Hassan Sarfraz; Hamna Yaseen; Muhammad Shahid Riaz Rajoka; Asad Ali Shah; Mohsin Khurshid (Biotechnology Letters, 2023)

Haemodialysis alters the serum metal contents in chronic kidney failure patients at hyderabad and adjoining areas - Marvi Shaikh; Naseem Aslam Channa; Ali Muhammad Wahryah; Muhammad Haneef Mugheri; Shakil Samejo; Lubna Noorani (BioMetals, 2023)

Climate-induced optimal wheat cropping season and mapping districts vulnerabilities in Punjab, Pakistan - Azhar Ali Janjua; Muhammad Aslam (Environment, Development and Sustainability, 2023)

Spatial distribution, compositional profile, sources, ecological and human health risks of legacy and emerging per- and polyfluoroalkyl substances (PFASs) in freshwater reservoirs of Punjab, Pakistan - Rahat Riaz; Muhammad Junaid; Muhammad Yasir Abdur Rehman; Taimoor Iqbal; Jawad Aslam Khan; Yanran Dong; Linxia Yue; Yupeng Chen; Nan Xu; Riffat Naseem Malik (Science of The Total Environment, 2023)

Applications of machine learning in thermochemical conversion of biomass-A review - Muzammil khan; Salman Raza Naqvi; Zahid Ullah; Syed Ali Ammar Taqvi; Muhammad Nouman Aslam Khan; Wasif Farooq; Muhammad Taqi Mehran; Dagmar Juchelková; Libor Štěpanec (Fuel, 2023)

Phytoremediation of Metal-Contaminated Soils and Water in Pakistan: a Review - Muhammad Shahbaz Akhtar; Ahmad Hameed; Sohaib Aslam; Razi Ullah; Aima Kashif (Water, Air, & Soil Pollution, 2023)

Characterization and expression analysis of basic leucine zipper (bZIP) transcription factors responsive to chilling injury in peach fruit - Muhammad Muzammal Aslam; Li Deng; Junren Meng; Yan Wang; Lei Pan; Liang Niu; Zhenhua Lu; Guochao Cui; Wenfang Zeng; Zhiqiang Wang (Molecular Biology Reports, 2023)

Microplastics in water, sediments, and fish at Alpine River, originating from the Hindu Kush Mountain, Pakistan: implications for conservation - Muhammad Bilal; Abdul Qadir; Atif Yaqub; Habib Ul Hassan; Muhammad Irfan; Mehmood Aslam (Environmental Science and Pollution Research, 2023)

Discovering patterns in the topography of existing settlements: the case of the China-Pakistan Economic Corridor (CPEC) route - Ahsen Maqsoom; Bilal Aslam; Umer Khalil; Sheheryar Azam; Zaheer Abbas Kazmi; Muhammad Usman Arif Rana (Arabian Journal of Geosciences, 2023)

Neopestalotiopsis guajavicola sp. nov. causing a new leaf spot on Psidium guajava in Pakistan - Imran Ul Haq; Siddra Ijaz; Nabeeha Aslam Khan; Anjum Faraz; Muhammad Kaleem Sarwar (Journal of Plant Pathology, 2022)

Landslide hazard, susceptibility and risk assessment (HSRA) based on remote sensing and GIS data models: a case study of Muzaffarabad Pakistan - Muhammad Nasar Ahmad; Zhenfeng Shao; Rana Waqar Aslam; Israr Ahmad; Ming Liao; Xianyi Li; Yang Song (Stochastic Environmental Research and Risk Assessment, 2022)

First report of cucumber-infecting cucurbit chlorotic yellows virus (CCYV) associated with cucurbit yellows disease in Pakistan - Muhammad Nouman; Tahir Farooq; Rashida Parveen; Ummad ud-Din Umar; Muhammad Naveed Aslam; Mahmoud Moustafa; Muhammad Taimoor Shakeel (Journal of Plant Pathology, 2022)

Correction to: Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

First report of post-harvest brown spot of lemon caused by Alternaria alternata in Pakistan - Anam Moosa; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel; Tanvir Ahmad; Mahmoud Moustafa; Mohammed Al-Shehri; Ahmed Al-Emam (Journal of Plant Pathology, 2022)

Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

Damage assessment of stored grain pests against rice grains types and wheat - Muhammad Waqar Hassan; Mohsin Ali Hashmi; Ghulam Sarwar; Zahid Mehmood; Warda Saleem; Muhammad Aslam Farooqi (International Journal of Tropical Insect Science, 2022)

GRAS transcription factors emerging regulator in plants growth, development, and multiple stresses - Muhammad Waseem; Oswald Nkurikiyimfura; Sylvain Niyitanga; Bello Hassan Jakada; Iffat Shaheen; Mehtab Muhammad Aslam (Molecular Biology Reports, 2022)

Evaluation of multi-satellite precipitation products for soil loss and sediment export modeling over eastern regions of the Koshi River Basin, Nepal - Belayneh Yigez; Donghong Xiong; Marye Belete; Baojun Zhang; Belayneh Azene; Muhammad Aslam Baig; Qin Xiao Min; Dil Kumar Rai; Nirmal Mani Dahal; Yanhong Wu; Zhang Wenduo (Journal of Soils and Sediments, 2022)

The Interactive Effect of Selenium and Farmyard Manure on Soil Microbial Activities, Yield and Selenium Accumulation by Wheat (Triticum aestivum L.) Grains - Muhammad Usman Khalid; Muhammad Imran; Muhammad Aslam; Muhammad Ashraf (Journal of Plant Growth Regulation, 2022)

Correction to: Awareness regarding COVID‑19 and its effects on mental health among pre‑professional health sciences students at King Saud bin Abdulaziz University for health sciences in Riyadh and Jeddah, Saudi Arabia - Zackary Alghamdy; Ashwaq Alshahrani; Ismail Memon; Aslam Khan; Muhammad Anwar Khan; Yazeed Alrayani; Fulwah Alfawzan; Syed Faisal Zaidi (Environmental Science and Pollution Research, 2022)

Awareness regarding COVID-19 and its effects on mental health among pre-professional health sciences students at King Saud bin Abdulaziz University for health sciences in Riyadh and Jeddah, Saudi Arabia - Zackary Alghamdy; Ashwaq Alshahrani; Ismail Memon; Aslam Khan; Muhammad Anwar Khan; Yazeed Alrayani; Fulwah Alfawzan; Syed Faisal Zaidi (Environmental Science and Pollution Research, 2022)

An Investigation of Landslide Susceptibility Using Logistic Regression and Statistical Index Methods in Dailekh District, Nepal - Dil Kumar Rai; Donghong Xiong; Wei Zhao; Dongmei Zhao; Baojun Zhang; Nirmal Mani Dahal; Yanhong Wu; Muhammad Aslam Baig (Chinese Geographical Science, 2022)

Effects of dam on temperature, humidity and precipitation of surrounding area: a case study of Gomal Zam Dam in Pakistan - Jamil Afzal; Zhou Yihong; Maria Qayum; Usama Afzal; Muhammad Aslam (Environmental Science and Pollution Research, 2022)

A novel lens of stock market capitalization and environmental degradation - Aamir Azeem; Muhammad Akram Naseem; Naveed Ul Hassan; Ijaz Butt; Muhammad Toseef Aslam; Shahid Ali; Atif khan Jadoon (Environmental Science and Pollution Research, 2022)

Point prevalence survey to estimate antimicrobial use in a tertiary care university hospital in Pakistan using WHO methodology: findings and implications - Muhammad Sharif; Sana Aslam; Zikria Saleem (Infectious Diseases, 2022)

How do multiple kernel functions in machine learning algorithms improve precision in flood probability mapping? - Muhammad Aslam Baig; Donghong Xiong; Mahfuzur Rahman; Md. Monirul Islam; Ahmed Elbeltagi; Belayneh Yigez; Dil Kumar Rai; Muhammad Tayab; Ashraf Dewan (Natural Hazards, 2022)

Antidiarrheal and antispasmodic activities of Trillium govanianum rhizomes extract: involvement of calcium channel blockade - Naveed Muhammad; Shafiq Ur Rahman; Hilal Uddin; Omer Shehzad; Muhammad Ismail; Niaz Ali; Aslam Khan; Muhammad Shahid; Abid Ullah; Shujaat Ahmad; Haya Hussain; Ikram ul Haq; et al. (Natural Product Research, 2022)

Pcal_2031, a RecA/Rad51 homologue from Pyrobaculum calidifontis, complements the ultraviolet light sensitivity of Escherichia coli - Syed Nasim Abbas; Mehwish Aslam; Amina Maqsood; Hafiza Zumra Fatima; Muhammad Arshad Javed; Naeem Rashid (Biologia, 2022)

Sustainable Conversion of Wastes into Green Bioproducts to Introduce Diversification and Green Economy in the Sugar Industry. A Review - Noé Aguilar-Rivera; Muhammad Tahir Khan; Imtiaz Ahmed Khan; Rashid Iqbal; Muhammad Mahran Aslam (Sugar Tech, 2022)

Isolation of the 3β-HSD promoter from Digitalis ferruginea subsp. ferruginea and its functional characterization in Arabidopsis thaliana - Noreen Aslam; Muhammad Sameeullah; Muhammet Yildirim; Mehmet Cengiz Baloglu; Buhara Yucesan; Andreas G. Lössl; Mohammad Tahir Waheed; Ekrem Gurel (Molecular Biology Reports, 2022)

Hydrogen peroxide priming alleviates salinity induced toxic effect in maize by improving antioxidant defense system, ionic homeostasis, photosynthetic efficiency and hormonal crosstalk - Muhammad Umer Chattha; Muhammad Uzair Ul Hassan; Imran Khan; Muhammad Nawaz; Adnan Noor Shah; Abdul Sattar; Mohamed Hashem; Saad Alamri; Muhammad Talha Aslam; Haifa A. S. Alhaithloul; Muhammad Umair Hassan; Sameer H. Qari (Molecular Biology Reports, 2022)

Carica papaya ameliorates thrombocytopenia through upregulation of Interleukin-11 and modulation of thrombopoietin in mouse model of carboplatin-induced myelosuppression - Sabeen Irshad; Arham Shabbir; Hina Aslam; Tasleem Akhtar; Muhammad Shahzad (Molecular Biology Reports, 2022)

Pharmacological evaluation of anti-arthritic potential of terpinen-4-ol using in vitro and in vivo assays - Sania Aslam; Waqas Younis; Muhammad Nasir Hayat Malik; Shah Jahan; Alamgeer; Ambreen Malik Uttra; Muhammad Usman Munir; Muhammad Roman (Inflammopharmacology, 2022)

A mini-review: positive impact of COVID-19 on Arial health and ecology - Sidra Naseer; Zhenggui Wei; Muhammad Shamrooz Aslam; Saira Naseer (Environmental Science and Pollution Research, 2022)

Wind energy potential assessment using Weibull distribution with various numerical estimation methods: a case study in Mersing and Port Dickson, Malaysia - Muhammad Aslam Mohd Safari; Nurulkamal Masseran; Muhammad Hilmi Abdul Majid (Theoretical and Applied Climatology, 2022)

Development of Basmati lines by the introgression of three bacterial blight resistant genes through marker-assisted breeding - Allah Ditta Babar; Abha Zaka; Shahzad Amir Naveed; Niaz Ahmad; Kashif Aslam; Muhammad Asif; Umer Maqsood; Casiana M. Vera Cruz; Muhammad Arif (Euphytica, 2022)

Exogenous melatonin mitigates chromium toxicity in maize seedlings by modulating antioxidant system and suppresses chromium uptake and oxidative stress - Zaffar Malik; Sobia Afzal; Muhammad Dawood; Ghulam Hassan Abbasi; Muhammad Imran Khan; Muhammad Kamran; Mostafa Zhran; Malik Tahir Hayat; Muhammad Naveed Aslam; Muhammad Rafay (Environmental Geochemistry and Health, 2022)

Evaluation of ceiling fan dust as an indicator of indoor PCBs pollution in selected cities of Punjab, Pakistan: implication on human health - Foqia Khalid; Abdul Qadir; Muhammad Zaffar Hashmi; Adeel Mehmood; Iqra Aslam; Gan Zhang; Zulkifl Ahmed (Arabian Journal of Geosciences, 2022)

Evaluation of insecticidal activity of Beauveria bassiana against different instar larvae of Plutella xylostella by using two different methods of application - Muhammad Shehzad; Muhammad Tariq; Qurban Ali; Asad Aslam; Tariq Mukhtar; Muhammad Faheem Akhtar; Asim Gulzar; Muhammad Faisal (International Journal of Tropical Insect Science, 2022)

Susceptibility of Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) on detached plant parts of transgenic and non-transgenic cotton - Muhammad Jawad Saleem; Faisal Hafeez; Qurban Ali; Asad Aslam; Muhammad Arshad; Dilbar Hussain; Ayesha Iftikhar; Afifa Naeem; Muhammad Saleem (International Journal of Tropical Insect Science, 2022)

A modified approach to quantify aquifer vulnerability to pollution towards sustainable groundwater management in Irrigated Indus Basin - Muhammad Umar; Shahbaz Nasir Khan; Arfan Arshad; Rana Ammar Aslam; Hafiz Muhammad Safdar Khan; Haroon Rashid; Quoc Bao Pham; Abdul Nasir; Rabeea Noor; Khaled Mohamed Khedher; Duong Tran Anh (Environmental Science and Pollution Research, 2022)

Financial impact of energy efficiency and energy policies aimed at power sector reforms: mediating role of financing in the power sector - Hongda Liu; Abdul Razzaq Khan; Sumaira Aslam; Abdul Khaliq Rasheed; Muhammad Mohsin (Environmental Science and Pollution Research, 2022)

Hydrological evaluation of 14 satellite-based, gauge-based and reanalysis precipitation products in a data-scarce mountainous catchment - Naeem Saddique; Muhammad Muzammil; Istakhar Jahangir; Abid Sarwar; Ehtesham Ahmed; Rana Ammar Aslam; Christian Bernhofer (Hydrological Sciences Journal, 2022)

Bio-diesel production of sunflower through sulphur management in a semi-arid subtropical environment - Athar Mahmood; Masood Iqbal Awan; Sana Sadaf; Ahmed Mukhtar; Xiukang Wang; Sajid Fiaz; Sher Aslam Khan; Habib Ali; Faran Muhammad; Zafar Hayat; Farhana Gul; Shah Fahad (Environmental Science and Pollution Research, 2022)

Assessment of major food crops production-based environmental efficiency in China, India, and Pakistan - Muhammad Shoaib Aslam; Pan Huanxue; Sidra Sohail; Muhammad Tariq Majeed; Saeed ur Rahman; Shoaib Ahmad Anees (Environmental Science and Pollution Research, 2022)

Aggregative effect on rice production due to climate change using index number under indeterminate environment: a case study from Punjab, Pakistan - Muhammad Aslam (Theoretical and Applied Climatology, 2022)

Intron-containing hairpin RNA interference vector for OBP8 show promising mortality in peach potato aphid - Amber Afroz; Safeena Aslam; Umer Rashid; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Muhammad Qasim Shahzad But; Sabaz Ali Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

A Review of Antimicrobial Peptides: Its Function, Mode of Action and Therapeutic Potential - Sehrish Nayab; Muhammad Aamir Aslam; Sajjad ur Rahman; Zia ud Din Sindhu; Sanaullah Sajid; Nishat Zafar; Maida Razaq; Rabia Kanwar; Amanullah (International Journal of Peptide Research and Therapeutics, 2022)

Multivariate geo-statistical perspective: evaluation of agricultural soil contaminated by industrial estate’s effluents - Muhammad Jamil; Ijaz Malook; Shafiq Ur Rehman; Muhammad Daud Khan; Muhammad Fayyaz; Muhammad Mudasar Aslam; Eui Shik Rha (Environmental Geochemistry and Health, 2022)

Lack of CpG islands in human unitary pseudogenes and its implication - Ammad Aslam Khan; Muhammad Shahryar Ali; Farah Babar; Anees Fatima; Muhammad Awais Shafqat; Bisma Asghar; Nimra Ilyas; Maheen Fatima; Ayesha Liaqat; Muhammad Aslam Gondal (Mammalian Genome, 2021)

Spatial distribution of soil erosion and sediment yield in the Koshi River Basin, Nepal: a case study of Triyuga watershed - Belayneh Yigez; Donghong Xiong; Baojun Zhang; Yong Yuan; Muhammad Aslam Baig; Nirmal Mani Dahal; Awoke Guadie; Wei Zhao; Yanhong Wu (Journal of Soils and Sediments, 2021)

Green Synthesis of Silver Nitrate Nanoparticles from Camelina Sativa (L.) and Its Effect to Control Insect Pests of Stored Grains - Habib ur Rehman; Beenish Majeed; Muhammad Aslam Farooqi; Amer Rasul; Muhammad Sagheer; Qurban Ali; Zunnu Raen Akhtar (International Journal of Tropical Insect Science, 2021)

Assessing the potential of partial root zone drying and mulching for improving the productivity of cotton under arid climate - Rashid Iqbal; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Muhammad Waqas; Rao Muhammad Ikram; Muhammad Zeshan Ahmed; Monika Toleikiene; Muhammad Ayaz; Farhan Mustafa; Salman Ahmad; Muhammad Usman Aslam; Muhammad Mohsin Waqas; et al. (Environmental Science and Pollution Research, 2021)
Water scarcity constrains global cotton production. However, partial root-zone drying (PRD) and mulching can be used as good techniques to save water and enhance crop production, especially in arid regions. This study aimed to evaluate the effects of mulching for water conservation in an arid environment under PRD and to further assess the osmotic adjustment and enzymatic activities for sustainable cotton production. The study was carried out for 2 years in field conditions using mulches (NM = no mulch, BPM = black plastic mulch at 32 kg ha -1 , WSM = wheat straw mulch at 3 tons ha -1 , CSM = cotton sticks mulch at 10 tons ha -1 ) and two irrigation levels (FI = full irrigation and PRD (50% less water than FI). High seed cotton yield (SCY) achieved in FI+WSM (4457 and 4248 kg ha -1 in 2017 and 2018, respectively) and even in PRD+WSM followed by BPM>CSM>NM under FI and PRD for both years. The higher SCY and traits observed in FI+WSM and PRD+WSM compared with the others were attributed to the improved water use efficiency and gaseous exchange traits, increased hormone production (ABA), osmolyte accumulation, and enhanced antioxidants to scavenge the excess reactive oxygen. Furthermore, better cotton quality traits were also observed under WSM either with FI or PRD irrigation regimes. Mulches applications found effective to control the weeds in the order as BPM>WSM>CSM. In general, PRD can be used as an effective stratagem to save moisture along with WSM, which ultimately can improve cotton yield in the water-scarce regions under arid climatic regions. It may prove as a good adaptation strategy under current and future water shortage scenarios of climate change.

Isolation of tyrosine derived phenolics and their possible beneficial role in anti-inflammatory and antioxidant potential of Tithonia tubaeformis - Noor Ul Ain Nawaz; Muhammad Saeed; Khalid Mohammed Khan; Irfan Ali; Huma Aslam Bhatti; Sabi-Ur-Rehman; Muhammad Shahid; Shaheen Faizi (Natural Product Research, 2021)

Correction to: First report of Alternaria alternata causing post‑harvest brown spot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Naveed Aslam; Tanvir Ahmad; Ambreen Maqsood; Muhammad Shafique (Journal of Plant Pathology, 2021)

First report of Alternaria alternata causing post-harvest brown spot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Naveed Aslam; Tanvir Ahmad; Ambreen Maqsood; Muhammad Shafique (Journal of Plant Pathology, 2021)

Integrated support vector regressor and hybrid neural network techniques for earthquake prediction along Chaman fault, Baluchistan - Umer Khalil; Bilal Aslam; Zaheer Abbas Kazmi; Ahsen Maqsoom; Muhammad Irshad Qureshi; Sheheryar Azam; Ahsan Nawaz (Arabian Journal of Geosciences, 2021)

Exposure of broiler chickens to chronic heat stress increases the severity of white striping on the pectoralis major muscle - Muhammad Adnan Aslam; Emrah İpek; Roshan Riaz; Şule Yurdagül Ӧzsoy; Waseem Shahzad; Ӧzay Güleş (Tropical Animal Health and Production, 2021)

Tomato COI gene family identification and expression under abiotic and phytohormone stress - Muhammad Waseem; Mehtab Muhammad Aslam; Iffat Shaheen (Journal of Genetics, 2021)

Gradient-based impedance synthesis for breast and lung cancer cell screening deploying planar and nano-structured electrodes - Muhammad Awais Aslam; Kashif Riaz; Muhammad Mubasher Saleem (Medical & Biological Engineering & Computing, 2021)

Paclobutrazol Improves Sesame Yield by Increasing Dry Matter Accumulation and Reducing Seed Shattering Under Rainfed Conditions - Muhammad Zeeshan Mehmood; Ghulam Qadir; Obaid Afzal; Atta Mohi Ud Din; Muhammad Ali Raza; Imran Khan; Muhammad Jawad Hassan; Samrah Afzal Awan; Shakeel Ahmad; Muhammad Ansar; Muhammad Aqeel Aslam; Mukhtar Ahmed (International Journal of Plant Production, 2021)
Several biotic and abiotic stresses significantly decrease the biomass accumulation and seed yield of sesame crops under rainfed areas. However, plant growth regulators (such as Paclobutrazol) can improve the total dry matter and seed production of the sesame crop. The effects of the paclobutrazol application on dry matter accumulation and seed yield had not been studied before in sesame under rainfed conditions. Therefore, a two-year field study during 2018 and 2019 was conducted with key objectives to assess the impacts of paclobutrazol on leaf greenness, leaf area, total dry matter production and partitioning, seed shattering, and seed yield of sesame. Two sesame cultivars (TS-5 and TS-3) were treated with four paclobutrazol concentrations (P0 = Control, P1 = 100 mg L −1 , P2 = 200 mg L −1 , P3 = 300 mg L −1 ). The experiment was executed in RCBD-factorial design with three replications. Compared with P0, treatment P3 improved the leaf greenness of sesame by 17%, 38%, and 60% at 45, 85, and 125 days after sowing, respectively. However, P3 treatment decreased the leaf area of sesame by 14% and 20% at 45 and 85 days after sowing than P0, respectively. Compared with P0, treatment P3 increased the leaf area by 46% at 125 days after sowing. On average, treatment P3 also improved the total biomass production by 21% and partitioning in roots, stems, leaves, capsules, and seeds by 23%, 19%, 23%, 22%, and 40%, respectively, in the whole growing seasons as compared to P0. Moreover, under P3 treatment, sesame attained the highest seed yield and lowest seed shattering by 27% and 30%, respectively, compared to P0. This study indicated that by applying the paclobutrazol concentration at the rate of 300 mg L −1 in sesame, the leaf greenness, leaf areas, biomass accumulation, partitioning, seed yield, and shatter resistance could be improved. Thus, the optimum paclobutrazol level could enhance the dry matter accumulation and seed production capacity of sesame by decreasing shattering losses under rainfed conditions.

Determination of pesticide residues in dates using UHPLC-QqQ-MS/MS: method development and validation - Somia Qayyum; Touqeer Taj; Muhammad Tauseef; Muhammad Ishtiaq; Nazia Rafique; Karam Ahad; Muhammad Aslam Mirza; Muhammad Aziz Choudhary; Farrakh Mehboob (Environmental Monitoring and Assessment, 2021)

Enhanced statistical tests under indeterminacy with application to earth speed data - Muhammad Aslam (Earth Science Informatics, 2021)

Asymmetric macroeconomic determinants of CO2 emission in China and policy approaches - Bilal Aslam; Jinsong Hu; Muhammad Tariq Majeed; Zubaria Andlib; Sana Ullah (Environmental Science and Pollution Research, 2021)

Assessment of rice and wheat production efficiency based on data envelopment analysis - Muhammad Shoaib Aslam; Pan Huan Xue; Shahid Bashir; Yazeed Alfakhri; Mohammad Nurunnabi; Van Chien Nguyen (Environmental Science and Pollution Research, 2021)

The role of financial development indicators in sustainable development-environmental degradation nexus - Xiaolong Li; Zhiyuan Yu; Asma Salman; Qaisar Ali; Muhammad Hafeez; Muhammad Shoaib Aslam (Environmental Science and Pollution Research, 2021)

Wind speed pattern data and wind energy potential in Pakistan: current status, challenging platforms and innovative prospects - Hammad Saulat; Muhammad Masood Khan; Muhammad Aslam; Muhammad Chawla; Sikander Rafiq; Faisal Zafar; Muhammad Mahmood Khan; Awais Bokhari; Farrukh Jamil; Abdul Waheed Bhutto; Aqeel Ahmed Bazmi (Environmental Science and Pollution Research, 2021)

CO2 separation by supported liquid membranes synthesized with natural deep eutectic solvents - Usman Saeed; Asim Laeeq Khan; Mazhar Amjad Gilani; Muhammad Aslam; Asad Ullah Khan (Environmental Science and Pollution Research, 2021)

Human and ecological risk assessment of heavy metals in different particle sizes of road dust in Muscat, Oman - Hilal K. Al-Shidi; Hameed Sulaiman; Hassan A. Al-Reasi; Farrukh Jamil; Muhammad Aslam (Environmental Science and Pollution Research, 2021)

Correction to: Anomaly Classification for Earthquake Prediction in Radon Time Series Data Using Stacking and Automatic Anomaly Indication Function - Adil Aslam Mir; Fatih Vehbi Çelebi; Muhammad Rafique; M. R. I. Faruque; Mayeen Uddin Khandaker; Kimberlee Jane Kearfott; Pervaiz Ahmad (Pure and Applied Geophysics, 2021)

Microfacies analysis and reservoir evaluation based on diagenetic features and log analysis of the Nammal Formation, Western and Central Salt Range, Upper Indus Basin, Pakistan - Jabir Hussain; Tahseenullah Khan; Birkhez Aslam Shami; Muhammad Zafar; Tassawar Hayat (Arabian Journal of Geosciences, 2021)

Anomaly Classification for Earthquake Prediction in Radon Time Series Data Using Stacking and Automatic Anomaly Indication Function - Adil Aslam Mir; Fatih Vehbi Çelebi; Muhammad Rafique; M. R. I. Faruque; Mayeen Uddin Khandaker; Kimberlee Jane Kearfott; Pervaiz Ahmad (Pure and Applied Geophysics, 2021)

Synthesis, characterization, antimicrobial, antioxidant and computational evaluation of N-acyl-morpholine-4-carbothioamides - Hamid Aziz; Aamer Saeed; Muhammad Aslam Khan; Shakeeb Afridi; Farukh Jabeen (Molecular Diversity, 2021)

First report of Curvularia leaf spot of Chamaedorea seifrizii caused by Curvularia lunata in Pakistan - Imran Ul haq; Siddra Ijaz; Anjum Faraz; Muhammad Kaleem Sarwar; Nabeeha Aslam Khan (Journal of Plant Pathology, 2021)

The impact of financial development, political institutions, and urbanization on environmental degradation: evidence from 59 less-developed economies - Iftikhar Yasin; Nawaz Ahmad; Muhammad Aslam Chaudhary (Environment, Development and Sustainability, 2021)

Can sulphur improve the nutrient uptake, partitioning, and seed yield of sesame? - Muhammad Zeeshan Mehmood; Obaid Afzal; Mukhtar Ahmed; Ghulam Qadir; Ahmed M.S. Kheir; Muhammad Aqeel Aslam; Atta Mohi Ud Din; Imran Khan; Muhammad Jawad Hassan; Tehseen Ahmad Meraj; Muhammad Ali Raza; Shakeel Ahmad (Arabian Journal of Geosciences, 2021)
Sulphur (S) is considered to improve the nutrient uptake of plants due to its synergistic relationship with other nutrients. This could ultimately enhance the seed yield of oilseed crops. However, there is limited quantitative information on nutrient uptake, distribution, and its associated impacts on seed yield of sesame under the S application. Thus, a two-year field study (2018 and 2019) was conducted to assess the impacts of different S treatments (S 0 = Control, S 20 = 20, S 40 = 40, and S 60 = 60 kg ha −1 ) on total dry matter production, nitrogen, phosphorus, potassium, S uptake and distribution at the mid-bloom stage and physiological maturity. Furthermore, treatment impacts were studied on the number of capsules per plant, number of seeds per capsule, thousand seed weight, and seed yield at physiological maturity in sesame. Compared to S 0 , over the years, treatment S 40 significantly increased the total uptake of nitrogen, phosphorus, potassium, and S (by 13, 22, 11% and 16%, respectively) at physiological maturity, while their distribution by 13, 36, 14, and 24% (in leaves), 12, 15, 11, and 15% (in stems), 15, 42, 18, and 10% (in capsules), and 14, 22, 9, and 15% (in seeds), respectively. Enhanced nutrient uptake and distribution in treatment S 40 improved the total biomass accumulation (by 28%) and distribution in leaves (by 34%), stems (by 27%), capsules (by 26%), and seeds (by 28%), at physiological maturity, as compared to S 0 . Treatment S 40 increased the number of capsules per plant (by 13%), number of seeds per capsule (by 11%), and thousand seed weight (by 6%), compared to S 0 . Furthermore, over the years, relative to control, sesame under S 40 had a higher seed yield by 28% and enhanced the net economic returns by 44%. Thus, our results suggest that optimum S level at the time of sowing improves the nutrient uptake and distribution during the plant lifecycle, which ultimately enhances total dry matter accumulation, seed yield, and net productivity of sesame.

Insights into the mechanisms of arsenic-selenium interactions and the associated toxicity in plants, animals, and humans: A critical review - Waqar Ali; Hua Zhang; Muhammad Junaid; Kang Mao; Nan Xu; Chuanyu Chang; Atta Rasool; Muhammad Wajahat Aslam; Jamshed Ali; Zhugen Yang (Critical Reviews in Environmental Science and Technology, 2021)

Investigating the effect of Aspergillus niger inoculated press mud (biofertilizer) on the potential of enhancing maize (Zea mays L.) yield, phosphorous use efficiency, and phosphorous agronomic efficiency - Urooj Naeem; Muhammad Afzaal; Irfan ul Haq; Akram Qazi; Abdullah Yasar; Amtul Bari Tabinda; Yusra Mahfooz; Asad Ullah Naz; Humera Aslam Awan; Ashfaq Ahmad (Arabian Journal of Geosciences, 2021)

Heat stress in cultivated plants: nature, impact, mechanisms, and mitigation strategies—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Lorenzo Barbanti; Muhammad Aamer; Muhammad Mehmood Iqbal; Muhammad Nawaz; Athar Mahmood; Abid Ali; Muhammad Talha Aslam (Plant Biosystems, 2021)

Appraisal of One Health approach amid COVID-19 and zoonotic pandemics: insights for policy decision - Muhammad Imran Arshad; Hilal Ahmad Khan; Bilal Aslam; Junaid Ali Khan (Tropical Animal Health and Production, 2021)

Extent and pattern of damage in wheat caused by three different species of storage insect pests - Muhammad Waqar Hassan; Ghulam Sarwar; Muhammad Aslam Farooqi; Moazzam Jamil (International Journal of Tropical Insect Science, 2021)

CO2 from waste to resource by developing novel mixed matrix membranes - Adeel Shakoor; Asim Laeeq Khan; Parveen Akhter; Muhammad Aslam; Muhammad Roil Bilad; Ibrahim M. Maafa; Konstantinos Moustakas; Abdul-Sattar Nizami; Murid Hussain (Environmental Science and Pollution Research, 2021)

A study on skewness and kurtosis estimators of wind speed distribution under indeterminacy - Muhammad Aslam (Theoretical and Applied Climatology, 2021)

Carbon, nitrogen, and phosphorus stoichiometry mediate sensitivity of carbon stabilization mechanisms along with surface layers of a Mollisol after long-term fertilization in Northeast China - Muhammad Mohsin Abrar; Hu Xu; Tariq Aziz; Nan Sun; Adnan Mustafa; Muhammad Wajahat Aslam; Syed Atizaz Ali Shah; Khalid Mehmood; Baoku Zhou; Xingzhu Ma; Xianni Chen; Minggang Xu (Journal of Soils and Sediments, 2021)

First report of leaf spot of bottle gourd (Lagenaria siceraria) caused by Fusarium equiseti in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Sabin Aslam; Muhammad Amjad Ali; Nasir Ahmad Khan; Yingyan Zhai; Mark L. Gleason (Journal of Plant Pathology, 2021)

Organoid culture to study epithelial cell differentiation and barrier formation in the colon: bridging the gap between monolayer cell culture and human subject research - James Varani; Shannon D. McClintock; Muhammad Nadeem Aslam (In Vitro Cellular & Developmental Biology - Animal, 2021)

Systematic study of the new remains of Propotamochoerus hysudricus (Suidae, Mammalia) from the Late Miocene–Early Pliocene of Middle Siwaliks (Pakistan) - Sadaf Aslam; Abdul Majid Khan; Rana Manzoor Ahmad; Ayesha Iqbal; Muhammad Tahir Waseem (Arabian Journal of Geosciences, 2021)

Influence of Extraction Variables on Free Radical Scavenging Potential of Nelumbo nucifera Seed Kernel: Optimization by Response Surface Methodology - Haq Nawaz; Muhammad Aslam Shad; Sabiha Tahir Abbasi (Journal of Pharmaceutical Innovation, 2020)

Evaluating the relationship between climate variability and agricultural crops under indeterminacy - Azhar Ali Janjua; Muhammad Aslam; Naheed Sultana (Theoretical and Applied Climatology, 2020)

First report of brown leaf spot of rice caused by Curvularia spicifera in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Muhammad Atiq; Muhammad Zeeshan Mansha; Hafiz Muhammad Aatif; Hafiz Arslan Anwaar; Khalid Naveed (Journal of Plant Pathology, 2020)

Modeling the transition behaviors of PM10 pollution index - Nurulkamal Masseran; Muhammad Aslam Mohd Safari (Environmental Monitoring and Assessment, 2020)

RLP, a bacteriophage of the family Podoviridae, rescues mice from bacteremia caused by multi-drug-resistant Pseudomonas aeruginosa - Iqbal Ahmad Alvi; Muhammad Asif; Rabia Tabassum; Rehan Aslam; Zaigham Abbas; Shafiq ur Rehman (Archives of Virology, 2020)

Inorganic fertilization improves quality and biomass of Moringa oleifera L. - Muhammad Farhan Aslam; Shahzad M. A. Basra; Muhammad Bilal Hafeez; Shahbaz Khan; Sohail Irshad; Shahid Iqbal; Muhammad Sohail Saqqid; Muhammad Zubair Akram (Agroforestry Systems, 2020)

In-vitro evaluation of antimicrobial, antioxidant, alpha-amylase inhibition and cytotoxicity properties of Cannabis sativa - Syed Bilal Shah; Lubna Sartaj; Shahid Hussain; Nabi Ullah; Muhammad Idrees; Asma Shaheen; Muhammad Sufyan Javed; Muhammad Kashif Aslam (Advances in Traditional Medicine, 2020)

Synergistic Long-Term Temperate Climate Nitrogen Removal Performance in Open Raceway Pond and Horizontal Subsurface Flow Constructed Wetland Operated Under Different Regimes - Raana Fahim; Xiwu Lu; Ghulam Ahmad Jilani; Hasan Mahdi; Muhammad Aslam (Water, Air, & Soil Pollution, 2020)

First report of leaf spots in Caryota mitis L. caused by Alternaria alstroemeriae in Pakistan - Imran Ul haq; Siddra Ijaz; Anjum Faraz; Muhammad Kaleem Sarwar; Muhammad Zunair Latif; Nabeeha Aslam Khan (Journal of Plant Pathology, 2020)

A forecasting model approach of sustainable electricity management by developing adaptive neuro-fuzzy inference system - Aamir Nawaz Khan; Muhammad Asif Nadeem; Muhammad Shahid Hussain; Muhammad Aslam; Aqeel Ahmed Bazmi (Environmental Science and Pollution Research, 2020)

Risk assessment of extreme air pollution based on partial duration series: IDF approach - Nurulkamal Masseran; Muhammad Aslam Mohd Safari (Stochastic Environmental Research and Risk Assessment, 2020)

Valorization of solid waste biomass by inoculation for the enhanced yield of biogas - Yasir Abbas; Farrukh Jamil; Sikander Rafiq; Moinuddin Ghauri; M. Shahzad Khurram; Muhammad Aslam; Awais Bokhari; Abrar Faisal; Umer Rashid; Sining Yun; Muhammad Mubeen (Clean Technologies and Environmental Policy, 2020)

First report of Nigrospora sphaerica causing leaf spot of date palm in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Shahbaz Ahmad; Mubeen Sarwar; Aamir Nawaz; Samiya Mahmood Khan; Sajid Ali; Sidra Aslam; Abdul Mannan (Journal of Plant Pathology, 2020)

Assessment of noise pollution and its effects on human health in industrial hub of Pakistan - Zia Ur Rahman Farooqi; Muhammad Sabir; Junaid Latif; Zubair Aslam; Hamaad Raza Ahmad; Iftikhar Ahmad; Muhammad Imran; Predrag Ilić (Environmental Science and Pollution Research, 2020)

Photoperiodic stress induces genotype-specific shift in DNA methylation in Tartary buckwheat - Muhammad Saad; Helen Mary; Umar Amjid; Ghulam Shabir; Kashif Aslam; Shahid Masood Shah; Abdul Rehman Khan (Biologia Futura, 2019)
Tartary buckwheat, known for its rich source of health beneficial secondary metabolites, is cultivated in many areas of the world. Among different environmental factors, photoperiod strongly influence its growth, flowering time, and ultimately the yield. In this context, epigenetics could contribute significantly in the regulation of plant response against changing environment. Therefore, with the aim to study the involvement of DNA methylation in photoperiod mediated plant response, genome-wide DNA methylation analysis was performed in two accessions (A1 and A2) of Tartary buckwheat using three photoperiodic treatments, i.e., 10-hr light/day (T1), 12-hr light/day (T2), and 14-hr light/day (T3). Flowering time and plant fresh weight data revealed that accessions A1 and A2 prefer T1 and T2 treatments, respectively. Total DNA methylation ratio increased with the increase in photoperiod in accession A1 but decreased under same conditions in accession A2. Full methylation increased significantly while intensive decrease in hemimethylation was noted from T2 to T3 in A1, whereas full methylation strongly increased and hemimethylation strongly decreased from T1 to T2 in A2. Overall, the DNA methylation events appeared more frequently than demethylation events. This study reports for the first time an accession-/genotype specific pattern of shift in the DNA methylation under different photoperiodic treatments that will pave the way toward identification of specific genes involved in the regulation of plant response against photoperiodic stress.

Correction to: Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)

Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)

Role of Bioactive Peptides in Reducing the Severity of Hypertension with the Inhibition of ACE - Muhammad Zohaib Aslam; Muhammd Shoaib Aslam; Shumaila Firdos; Ghulam Ghous; Gulistan Firdos; Zhao Hongfei; Zhang Bolin (International Journal of Peptide Research and Therapeutics, 2019)

Peptidomic Analysis of ACE Inhibitory Peptides Extracted from Fermented Goat Milk - Muhammad Zohaib Aslam; Sana Shoukat; Zhao Hongfei; Zhang Bolin (International Journal of Peptide Research and Therapeutics, 2019)

Mixed matrix membranes incorporated with sonication-assisted ZIF-8 nanofillers for hazardous wastewater treatment - Mohsin Ali; Muhammad Aslam; Amin Khan; Mazhar Amjad Gilani; Asim Laeeq Khan (Environmental Science and Pollution Research, 2019)

Heat treatment effects on chilling injury and disease incidence in sweet orange fruits stored at chilling and non-chilling temperatures - Ijaz Hussain; Abdur Rab; Naqib Ullah Khan; Zarina Bibi; Shah Masaud Khan; Naushad Ali; Muhammad Saeed; Sher Aslam Khan; Sardar Ali; Ghulam Dastagir; Muhammad Sajid (Journal of Consumer Protection and Food Safety, 2019)

Identification of two further agriculturally important begomoviruses and their associated satellites infecting the weed Digera arvensis in Pakistan - Afzal Akram; Khalid Pervaiz Akhtar; Najeeb Ullah; Muhammad Qasim Aslam; Peter Moffett; Shahid Mansoor; Rob W. Briddon; Muhammad Saeed (European Journal of Plant Pathology, 2019)

Unraveling prevalence and public health risks of arsenic, uranium and co-occurring trace metals in groundwater along riverine ecosystem in Sindh and Punjab, Pakistan - Waqar Ali; Muhammad Wajahat Aslam; Caiyan Feng; Muhammad Junaid; Kamran Ali; Shehong Li; Zhe Chen; Ziheng Yu; Atta Rasool; Hua Zhang (Environmental Geochemistry and Health, 2019)

A Review on the Status of Mercury Pollution in Pakistan: Sources and Impacts - Waqar Ali; Muhammad Junaid; Muhammad Wajahat Aslam; Kamran Ali; Atta Rasool; Hua Zhang (Archives of Environmental Contamination and Toxicology, 2019)

Genetic polymorphism in association with susceptibility to tuberculosis: a study in a Pakistani population - AsmaGul Naz; Muhammad Assad Aslam; Abrar Ul Haq Khan; Sumaira Rasul; Hamid Manzoor; Rehana Iqbal; Ahmed Shehzad; Muhammad Ali (Brazilian Journal of Microbiology, 2019)

First report of Alternaria alternata causing postharvest fruit rot of peach in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Aman Ullah Malik; Sidra Aslam; Mubeen Sarwar; Sajid Ali; Muhammad Arslan Khan; Akhtar Hameed; Sohaib Sarfraz (Journal of Plant Pathology, 2019)

Investigating membrane fouling associated with GAC fluidization on membrane with effluent from anaerobic fluidized bed bioreactor in domestic wastewater treatment - Muhammad Aslam; Jeonghwan Kim (Environmental Science and Pollution Research, 2019)

Membrane scouring to control fouling under fluidization of non-adsorbing media for wastewater treatment - Muhammad Aslam; Amine Charfi; Jeonghwan Kim (Environmental Science and Pollution Research, 2019)

Classification of rocks radionuclide data using machine learning techniques - Abdul Razzaq Khan; Adil Aslam Mir; Sharjil Saeed; Muhammad Rafique; Khawaja M. Asim; Talat Iqbal; Abdul Jabbar; Saeed Ur Rahman (Acta Geophysica, 2018)

Effects of biochar on growth, photosynthesis, and chromium (Cr) uptake in Brassica rapa L. under Cr stress - Shafaqat Ali; Muhammad Rizwan; Ruqia Bano; Saima Aslam Bharwana; Muhammad Zia ur Rehman; Muhammad Bilal Hussain; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2018)

Changes in the nutritional composition of maize flour due to Tribolium castaneum infestation and application of carbon dioxide to manage this pest - Khalid Mehmood; Mureed Husain; Muhammad Aslam; Muhammad Shoaib Ahmedani; Azhar Mehmood Aulakh; Farid Asif Shaheen (Environmental Science and Pollution Research, 2018)

Phytochemical screening and in-vitro evaluation of pharmacological activities of peels of Musa sapientum and Carica papaya fruit - Sarmad Siddique; Shamsa Nawaz; Faqir Muhammad; Bushra Akhtar; Bilal Aslam (Natural Product Research, 2018)

Alkali-Activated Boiler Fly Ash for Ni(II) Removal: Characterization and Parametric Study - Muhammad Samiullah; Zaheer Aslam; Adeem Ghaffar Rana; Aamir Abbas; Waqar Ahmad (Water, Air, & Soil Pollution, 2018)

Distribution of IL28B and IL10 polymorphisms as genetic predictors of treatment response in Pakistani HCV genotype 3 patients - Humaira Naeemi; Rabia Aslam; Syed Mohsin Raza; Muhammad Aiman Shahzad; Shagufta Naz; Sobia Manzoor; Saba Khaliq (Archives of Virology, 2018)

Modeling the Air Pollution Index based on its structure and descriptive status - Nasr Ahmed AL-Dhurafi; Nurulkamal Masseran; Zamira Hasanah Zamzuri; Muhammad Aslam Mohd Safari (Air Quality, Atmosphere & Health, 2018)

Microfacies analysis and diagenetic fabric of the Lockhart Limestone exposed near Taxila, Margalla Hill Range, Punjab, Pakistan - Mohibullah Khan; Mumtaz Ali Khan; Birkhez Aslam Shami; Muhammad Awais (Arabian Journal of Geosciences, 2018)

Assessment of resistance to bacterial wilt incited by Ralstonia solanacearum in tomato germplasm - Muhammad Naveed Aslam; Tariq Mukhtar; Muhammad Arshad Hussain; Muhammad Raheel (Journal of Plant Diseases and Protection, 2017)

Evaluation of Green Waste and Popular Twigs Biochar Produced at Low and High Pyrolytic Temperature for Efficient Removal of Metals from Water - Zeshan Aslam; Muhammad Khalid; Muhammad Naveed; Muhammad Shahid; Muhammad Aon (Water, Air, & Soil Pollution, 2017)

Assessing the combined toxicity of conventional and newer insecticides on the cotton mealybug Phenacoccus solenopsis - Bushra Saddiq; Masood Ejaz; Sarfraz Ali Shad; Muhammad Aslam (Ecotoxicology, 2017)

Association of chili leaf curl betasatellite with tomato leaf curl disease - Muhammad Qasim Aslam; Khalid P. Akhtar; Mohy-u-Din Akram; Muhammad Y. Saleem; Nighat Sarwar; Sumaira Yousaf (Journal of General Plant Pathology, 2017)

Molecular and biologic characterization of a phytoplasma associated with Brassica campestris phyllody disease in Punjab province, Pakistan - Jam Nazeer Ahmad; Samina J. N. Ahmad; Muhammad Aslam; Muhammad Aijaz Ahmad; Nicoletta Contaldo; Samanta Paltrinieri; Assunta Bertaccini (European Journal of Plant Pathology, 2017)

Phenacyl group containing amide derivative of dehydroabietylamine exhibiting enhanced cytotoxic activity against PLC and MCF7 cancer cell lines - Muhammad Ayaz Mustufa; Afshan Aslam; Cigdem Ozen; Imran Ali Hashmi; Naim ul Hasan Naqvi; Mehmet Ozturk; Firdous Imran Ali (Medicinal Chemistry Research, 2017)

Vulnerability assessment of an agro-stressed aquifer using a source-pathway-receptor model in GIS - Yawar Hussain; Sadia F. Ullah; Abdul Q. Aslam; Muhammad B. Hussain; Gulraiz Akhter; Hernan E. Martinez-Carvajal; Frédéric Satgé; Arshad Ashraf; Bilal Iqbal; Martin Cárdenas-Soto (Modeling Earth Systems and Environment, 2017)

Biological control of broad-leaved dock infestation in wheat using plant antagonistic bacteria under field conditions - Tasawar Abbas; Zahir Ahmad Zahir; Muhammad Naveed; Zubair Aslam (Environmental Science and Pollution Research, 2017)

Physiological and biochemical mechanisms of silicon-induced copper stress tolerance in cotton (Gossypium hirsutum L.) - Shafaqat Ali; Muhammad Rizwan; Najeeb Ullah; Saima Aslam Bharwana; Muhammad Waseem; Muhammad Ahsan Farooq; Ghulam Hasan Abbasi; Mujahid Farid (Acta Physiologiae Plantarum, 2016)

Genetic diversity analysis of Pakistan rice (Oryza sativa) germplasm using multiplexed single nucleotide polymorphism markers - Shahid Masood Shah; Muhammad Arif; Kashif Aslam; Ghulam Shabir; Michael J. Thomson (Genetic Resources and Crop Evolution, 2016)

Comparative Study of Physical Factors and Microbial Diversity of Four Man-Made Extreme Ecosystems - Imran Ali; Ali Akbar; Muhammad Aslam; Sami Ullah; Muhammad Anwar; Hunsa Punnapayak; Pongtharin Lotrakul; Sehanat Prasongsuk; Benjawan Yanwisetpakdee; Ponlada Permpornsakul; Sudip K. Rakshit (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Effectiveness and benefit cost ratio of selected insecticides at different applicationon intervals for brinjal shoot and fruit borer, Leucinodes orbonalis (G.) management on brinjal, Solanum melongena (L.) at Sahiwal, Pakistan - Qudsia Yousafi; Muhammad Afzal; Muhammad Aslam; Allah Ditta Abid (Phytoparasitica, 2016)

Deltamethrin resistance in the cotton mealybug, Phenacoccus solenopsis Tinsley: Cross-resistance to other insecticides, fitness cost analysis and realized heritability - Bushra Saddiq; Naeem Abbas; Sarfraz Ali Shad; Muhammad Aslam; Muhammad Babar Shahzad Afzal (Phytoparasitica, 2016)

Synthesis and biological activities of 2-aminophenol-based Schiff bases and their structure–activity relationship - Muhammad Aslam; Itrat Anis; Rashad Mehmood; Lubna Iqbal; Samina Iqbal; Inamullah Khan; Muhammad Salman Chishti; Shagufta Perveen (Medicinal Chemistry Research, 2016)

Mechanisms of silicon-mediated alleviation of drought and salt stress in plants: a review - Muhammad Rizwan; Shafaqat Ali; Muhammad Ibrahim; Mujahid Farid; Muhammad Adrees; Saima Aslam Bharwana; Muhammad Zia-ur-Rehman; Muhammad Farooq Qayyum; Farhat Abbas (Environmental Science and Pollution Research, 2015)

The use of PCR technique in the identification of Mycobacterium species responsible for bovine tuberculosis in cattle and buffaloes in Pakistan - Farah Akhtar; Muhammad Tariq Javed; Aziz-ur-Rehman; Muhammad Nisar Khan; Pervez Akhtar; Sayed Misdaq Hussain; Muhammad Sohaib Aslam; Razia Kausar; Mehwish Qamar; Monica Cagiola (Tropical Animal Health and Production, 2015)

Citric acid enhances the phytoextraction of chromium, plant growth, and photosynthesis by alleviating the oxidative damages in Brassica napus L. - Sehar Afshan; Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Farhat Abbas; Muhammad Ibrahim; Muhammad Aamer Mehmood; Ghulam Hasan Abbasi (Environmental Science and Pollution Research, 2015)

Fulvic acid mediates chromium (Cr) tolerance in wheat (Triticum aestivum L.) through lowering of Cr uptake and improved antioxidant defense system - Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Sidra Kanwal; Qasim Ali; Muhammad Ibrahim; Rafaqat Ali Gill; Muhammad Daud Khan (Environmental Science and Pollution Research, 2015)

The effect of excess copper on growth and physiology of important food crops: a review - Muhammad Adrees; Shafaqat Ali; Muhammad Rizwan; Muhammad Ibrahim; Farhat Abbas; Mujahid Farid; Muhammad Zia-ur-Rehman; Muhammad Kashif Irshad; Saima Aslam Bharwana (Environmental Science and Pollution Research, 2015)

Methane flux from paddy vegetated soil: a comparison between biogas digested liquid and chemical fertilizer - Ankit Singla; Suresh Kumar Dubey; Muhammad Aslam Ali; Kazuyuki Inubushi (Wetlands Ecology and Management, 2015)

Contribution of greenhouse gas emissions during cropping and fallow seasons on total global warming potential in mono-rice paddy soils - Md. Mozammel Haque; Sang Yoon Kim; Muhammad Aslam Ali; Pil Joo Kim (Plant and Soil, 2015)

Silicon-induced alleviation of NaCl toxicity in okra (Abelmoschus esculentus) is associated with enhanced photosynthesis, osmoprotectants and antioxidant metabolism - Tahira Abbas; Rashad Mukhtar Balal; Muhammad Adnan Shahid; Muhammad Aslam Pervez; Chaudhary Muhammad Ayyub; Muhammad Anjum Aqueel; Muhammad Mansoor Javaid (Acta Physiologiae Plantarum, 2015)

EDTA ameliorates phytoextraction of lead and plant growth by reducing morphological and biochemical injuries in Brassica napus L. under lead stress - Urooj Kanwal; Shafaqat Ali; Muhammad Bilal Shakoor; Mujahid Farid; Sabir Hussain; Tahira Yasmeen; Muhammad Adrees; Saima Aslam Bharwana; Farhat Abbas (Environmental Science and Pollution Research, 2014)

Synthesis, molecular docking and antiviral screening of novel N′-substitutedbenzylidene-2-(4-methyl-5,5-dioxido-3-phenylbenzo[e]pyrazolo[4,3-c][1,2]thiazin-1(4H)-yl)acetohydrazides - Sana Aslam; Matloob Ahmad; Muhammad Makshoof Athar; Usman Ali Ashfaq; John M. Gardiner; Catherine Montero; Mervi Detorio; Masood Parvez; Raymond F. Schinazi (Medicinal Chemistry Research, 2014)

Integrated effects of organic, inorganic and biological amendments on methane emission, soil quality and rice productivity in irrigated paddy ecosystem of Bangladesh: field study of two consecutive rice growing seasons - Muhammad Aslam Ali; M. A. Sattar; M. Nazmul Islam; K. Inubushi (Plant and Soil, 2014)

Hydrogen sulfide ameliorates lead-induced morphological, photosynthetic, oxidative damages and biochemical changes in cotton - Saima Aslam Bharwana; Shafaqat Ali; Muhammad Ahsan Farooq; Basharat Ali; Naeem Iqbal; Farhat Abbas; Muhammad Sajid Aqeel Ahmad (Environmental Science and Pollution Research, 2014)

Effect of heavy metal pollution on mineral absorption in sunflower (Helianthus annuus L.) hybrids - Unaiza Aslam; Iftikhar Ahmad; Mumtaz Hussain; Ameer Khan; Abdul Ghani; Irfan Mustafa; Sabahat Jalal; Muhammad Anjum Aqeel; Saira Asif; Haroon Ahmed (Acta Physiologiae Plantarum, 2014)

Preservation of Bone Structure and Function by Lithothamnion sp. Derived Minerals - Muhammad Nadeem Aslam; Ingrid Bergin; Karl Jepsen; Jaclynn M. Kreider; Kristin H. Graf; Madhav Naik; Steven A. Goldstein; James Varani (Biological Trace Element Research, 2013)

Maize seedling phosphorus nutrition: Allocation of remobilized seed phosphorus reserves and external phosphorus uptake to seedling roots and shoots during early growth stages - Muhammad Nadeem; Alain Mollier; Christian Morel; Muhammad Shahid; Muhammad Aslam; Muhammad Zia-ur-Rehman; Muhammad Ashfaq Wahid; Sylvain Pellerin (Plant and Soil, 2013)

Microsatellite analysis of Rosa damascena from Pakistan and Iran - Amjad Farooq; Mahnaz Kiani; Muhammad Aslam Khan; Atif Riaz; Asif Ali Khan; Natalie Anderson; David H. Byrne (Horticulture, Environment, and Biotechnology, 2013)

Mitigating Global Warming Potentials of Methane and Nitrous Oxide Gases from Rice Paddies under different irrigation regimes - Muhammad Aslam Ali; M. Anamul Hoque; Pil Joo Kim (Ambio, 2013)

Growth Control in Colon Epithelial Cells: Gadolinium Enhances Calcium-Mediated Growth Regulation - Durga Attili; Brian Jenkins; Muhammad Nadeem Aslam; Michael K. Dame; James Varani (Biological Trace Element Research, 2012)

Rs11892031[A] on chromosome 2q37 in an intronic region of the UGT1A locus is associated with urinary bladder cancer risk - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

A Multi-Mineral Natural Product Inhibits Liver Tumor Formation in C57BL/6 Mice - Muhammad N. Aslam; Ingrid Bergin; Madhav Naik; Anna Hampton; Ron Allen; Steven L. Kunkel; Howard Rush; James Varani (Biological Trace Element Research, 2012)

Characterization of a thermostable and alkaline xylanase from Bacillus sp. and its bleaching impact on wheat straw pulp - Mahjabeen Saleem; Farheen Aslam; Muhammad Saleem Akhtar; Mohsin Tariq; Muhammad Ibrahim Rajoka (World Journal of Microbiology and Biotechnology, 2012)

Stimulation of Fibroblast Proliferation by Insoluble Gadolinium Salts - Katherine Bleavins; Patricia Perone; Madhav Naik; Muneeb Rehman; Muhammad N. Aslam; Michael K. Dame; Sasha Meshinchi; Narasimharao Bhagavathula; James Varani (Biological Trace Element Research, 2012)

The unique role of siderophore in marine-derived Aureobasidium pullulans HN6.2 - Zhe Chi; Xing-Xing Wang; Zai-Chao Ma; Muhammad Aslam Buzdar; Zhen-Ming Chi (BioMetals, 2012)

Urinary bladder cancer risk in relation to a single nucleotide polymorphism (rs2854744) in the insulin-like growth factor-binding protein-3 (IGFBP3) gene - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Fibroblast Response to Lanthanoid Metal Ion Stimulation: Potential Contribution to Fibrotic Tissue Injury - William Jenkins; Patricia Perone; Kyle Walker; Narasimharao Bhagavathula; Muhammad Nadeem Aslam; Marissa DaSilva; Michael K. Dame; James Varani (Biological Trace Element Research, 2011)

Rs710521[A] on chromosome 3q28 close to TP63 is associated with increased urinary bladder cancer risk - Marie-Louise Lehmann; Silvia Selinski; Meinolf Blaszkewicz; Michael Orlich; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truss; Holger Gerullis; Thomas Otto; Dimitri Barski; et al. (Archives of Toxicology, 2010)

Production of a novel and cold-active killer toxin by Mrakia frigida 2E00797 isolated from sea sediment in Antarctica - Ming-Xia Hua; Zhe Chi; Guang-Lei Liu; Muhammad Aslam Buzdar; Zhen-Ming Chi (Extremophiles, 2010)

Nutrient digestibility and feedlot performance of lambs fed diets varying protein and energy contents - Javed I. Sultan; Asif Javaid; Muhammad Aslam (Tropical Animal Health and Production, 2010)

Human colon tissue in organ culture: preservation of normal and neoplastic characteristics - Michael K. Dame; Narasimharao Bhagavathula; Cohra Mankey; Marissa DaSilva; Tejaswi Paruchuri; Muhammad Nadeem Aslam; James Varani (In Vitro Cellular & Developmental Biology - Animal, 2010)

Chemical and biological characterization of siderophore produced by the marine-derived Aureobasidium pullulans HN6.2 and its antibacterial activity - Weilin Wang; Zhe Chi; Guanglei Liu; Muhammad Aslam Buzdar; Zhenming Chi; Qianqun Gu (BioMetals, 2009)

Heavy Metal Residues in the Milk of Cattle and Goats During Winter Season - Ijaz Javed; Ibadullah Jan; Faqir Muhammad; Zia-ur-Rahman; M. Zargham Khan; Bilal Aslam; Javed Iqbal Sultan (Bulletin of Environmental Contamination and Toxicology, 2009)

Effect of silicate fertilizer on reducing methane emission during rice cultivation - Muhammad Aslam Ali; Chang Hoon Lee; Pil Joo Kim (Biology and Fertility of Soils, 2008)